Non-contact monitoring of grouper fry weaning in recirculating aquaculture systems: Efficacy of an automated stereo vision system - Cheng-Yuan Kuo; Rung-Chi Lin; Tzong-Yueh Chen; Pei-Ju Chiang (Aquacultural Engineering, 2027)

The role of Mir-365-5p in regulating NF2-Mediated apoptosis and ROS production in hypoxic cardiomyoblasts - Chih-Hsueh Lin; Wei-Yun Wang; Bruce Chi-Kang Tsai; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Tsung-Jung Ho; Pei-Ying Pai; Dennis Jine-Yuan Hsieh; Chih-Yang Huang; Shinn-Zong Lin (Molecular Biology Reports, 2026)

Interpretable fault diagnosis in PWRs via hybrid deep learning models with root cause attribution and unseen fault incremental adaptation - Shadman Ahmad Khattak; Liu Yong-Kuo; Liu Yu-Kun; Shi Zhou-Xin; Yupeng Lin; Shiqi Wang; Shamsuddeen Lawal (Annals of Nuclear Energy, 2026)

Seismic rehabilitation of severely earthquake-damaged ductile RC T-shaped beams using mechanically anchored CFRP strips: Anchorage requirements and experimental validation - Chien-Kuo Chiu; Yi-Feng Lin; Hsin-Fang Sung; Lung-Cheng Hsieh (Engineering Structures, 2026)

Amorphous fluoropolymer OSRO membranes for highly-efficient hydrocarbon fractionation - Joy Thomas; Ning Gan; Hiroki Hayashi; Wakako Hashimoto; Natsuko Mikami; Tooru Kitagawa; Kuo-Lun Tung; Yuqing Lin; Hideto Matsuyama (Chemical Engineering Journal, 2026)

Future directions in oil spill modeling - Tor Nordam; Ana J. Abascal; Germán Aragón; Hossein Babaei; Christopher H. Barker; Kuo-Hsien Chang; Knut-Frode Dagestad; Rodrigo Duran; Deborah French-McCay; Melissa Gloekler; Aurelien Hospital; Panagiota Keramea; et al. (Ocean Modelling, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

Selective iron removal from Fe-PGMs alloys for platinum group metals concentration: Dissolution behavior of PGMs and ultrasound-assisted leaching - Han Yang; Yong Li; Xilong Wu; Ruiling Yuan; Chao Wang; Shengnan Lin; Jibiao Han; Kuo Liu (Journal of Environmental Chemical Engineering, 2026)

Flood-driven nutrient influx and phytoplankton succession in the subtropical waters of the Matsu Archipelago, Taiwan - Supriyadi; Yun-Chi Lin; Wan-Lin Chen; Kuo-Shu Chen; Gwo-Ching Gong; Sheng-Fang Tsai (Continental Shelf Research, 2026)

Material flow and sustainable utilization of end-of-life motorcycles under Taiwan’s vehicle electrification policy - Hsin-Tien Lin; Kuo-Che Weng; Daniel Sebastián Castillo-Castro (Waste Management, 2026)

Artificial intelligence-related technologies for municipal solid waste management: A review and new insights from smart cities - Tachin Chin; Ying Fan; Chien-Liang Lin; Yu-Cheng Lin; Kuo-Ti Liao (Sustainable Cities and Society, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Lithium-doped calcium silicate scaffolds induce miR-130a-rich M2 macrophage EV-accelerating diabetic bone healing through angiogenesis–osteogenic coupling and mitochondrial repair - Ting-You Kuo; Cheng-Yu Chen; Yen-Hong Lin; Der-Yang Cho; Tsung-Li Lin; Ming-You Shie (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Electrochemically functionalized MWCNT|ABTS nanocomposite: A versatile platform for dye recovery and upcycling for detection and valorization of nitroaromatics - Fitri Nur Indah Sari; Tien-Yu Kuo; Tzu-Hsuan Wang; Eunice Estrella De Guzman; Chia-Yu Lin (Journal of Environmental Chemical Engineering, 2026)

A compact, low-impact seismic source reshapes monitoring of offshore CO2 storage - Takeshi Tsuji; Tarek Imam; Ahmad Ahmad; Kazutoshi Sakamoto; Arata Kioka; Tetsuro Tsuru; Fernando Hutapea; Masaharu Ueki; Hao Kuo-Chen; Zhuo-Kang Guan; Chun-Hung Lin (International Journal of Greenhouse Gas Control, 2026)

Fine-scale post-fire forest recovery patterns and compound drivers in Taiwan’s high-mountain national parks - Chu-Chia Kuo; Yu-Ling Liu; Cheng-Tao Lin (Forest Ecology and Management, 2026)

Artificial intelligence-enabled flexible surface-enhanced Raman scattering substrate based on silver nanoparticles/polypyrrole/chitosan film for sensitive uric acid detection in saliva, serum and urine - Nazar Riswana Barveen; Petchi Raman Mariappan; Sathishkumar Chinnapaiyan; Yen-Yu Lin; Chih-Yu Kuo; Yu-Wei Cheng (Carbohydrate Polymers, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Cross‐Continental Differences in Climate Asymmetrically Shape Temporal Ecological Processes in Riverine Insect Diversity - Xiaowei Lin; Qingyi Luo; Mei‐Hwa Kuo; Zihao Wen; Qinghua Cai; Ming‐Chih Chiu; Vincent H. Resh (Global Change Biology, 2026)
Climatic fluctuations can play a crucial role in shaping large‐scale patterns of biodiversity and biogeography. This study examines how climatic gradients and their variability influence family‐level temporal ecological processes that govern the balance between stochastic and deterministic processes that underlie community dynamics of riverine insects. This comparison, done across multiple continents but mostly in the Northern Hemisphere, used long‐term data from 302 sites mainly in Europe, ranging from 10 to 37 years, and with 4751 observations of family‐level riverine insect assemblages. We analyzed spatial patterns in family richness, family‐level temporal beta diversity, and associated ecological processes. Generalized additive models revealed high spatial heterogeneity, with family‐level richness declining with latitude, but total family‐level temporal beta‐diversity decreasing with increasing latitude and elevation across the continents studied. The cross‐continental results from generalized additive and dissimilarity models further showed spatial shifts in the proxy indicators of ecological processes (e.g., environmental variables and time‐series decomposition), with stochastic processes (e.g., ecological drift) increasing in importance towards higher latitudes. In contrast, deterministic processes (e.g., temperature) declined. At a cross‐continental perspective, these findings highlight how spatial asymmetry under fluctuating climates may shape riverine insect community dynamics and improve adaptive conservation strategies.

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Synthesis of ZIF-8 derived porous carbon via morphology-controlled electrodeposited ZnO thin films for in-plane micro-supercapacitors - Jun-Yan Lin; Ramasamy Velmurugan; Jing-Jie Lin; Zhi-Ting Huang; Man-Ning Lu; Martin Hulman; Chien-Kuo Hsieh; Jeng-Yu Lin (Chemical Engineering Journal, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Design of mesoporous silica nanoparticles loaded with marine polysaccharides for enhanced antioxidant and skin-protective functions - Zui Harng Lee; Hsin-Chun Kuo; Showe-Mei Lin; Hsiu-Mei Lin (Food Bioscience, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Effect of somatosensory games on arterial stiffness and antioxidant status in postmenopausal women - Yi-Hung Liao; Kunanya Masodsai; Yu-Chi Kuo; Hsiao-Kuan Wu; Yi-Yuan Lin (European Journal of Applied Physiology, 2026)

Antioxidant and anti-aging activities of Salvia miltiorrhiza Bunge callus extracts in H2O2-induced premature senescence and chronological aging models of human dermal fibroblasts - Shinn-Zong Lin; Tzu-Kai Lin; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Yueh-Min Lin; Tsung-Jung Ho; Shang-Chuan Ng; Chih-Yang Huang (Biogerontology, 2026)

Integrating satellite tagging and remote sensing data to model the habitat selection behaviour of dolphinfish ( Coryphaena hippurus ) in the northwestern Pacific - Kuo-Wei Yen; Shian-Jhong Lin; Sheng-Ping Wang; Ryo Kawabe; Wei-Chuan Chiang (International Journal of Remote Sensing, 2026)

Carbon footprint assessment of Taiwan's aquaculture industry integrated with solar photovoltaics: A comprehensive review - Hsin-Yi Liu; Asif Ali Bhat; Yu-Wei Chen; Shin-Yu Chen; Ming-Kuei Shih; Kuo-Huan Ting; Chia-Hua Lin; Chih-Yao Hou (Aquaculture, 2026)

Integrating the cognitive-affective-conative model and stress appraisal theory for adventure tourism: The impact of challenge perception and motivation on revisit intention - Lu-Ping Lin; Nien-Te Kuo; Kuo-Chien Chang; Yi-Sung Cheng (Journal of Outdoor Recreation and Tourism, 2026)

Chicken sternum cartilage protein-chelated calcium: enhance bone density in vivo and in vitro, with insights into chelation mechanism - Shikun Suo; Yanli Wang; Lihui Du; Maolin Tu; Kuo Dang; Jingyi Chen; Yi Lin; Yali Dang; Qingqing Li (Food Research International, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

The Effects of Lactobacillus paracasei NB23 on IGF-1, Muscle Function, and Cardiometabolic Risk Factors in Healthy Individuals: A Randomized Controlled Trial - Su‑Wen Lin; Wang-Sheng Ko; Fang-Chuan Kuo; Hsueh-Fang Wang (Probiotics and Antimicrobial Proteins, 2026)

Regulated deficit irrigation strategy for greenhouse melons based on water status classification model and crop coefficient–reference evapotranspiration approach - Shih-Lun Fang; Bing-Yun Tsai; Sheng-Chih Chang; Yi-Lung Chang; Min-Hwi Yao; Ming-Kun Chi; Wen-Lin Wang; Bo-Jein Kuo (Irrigation Science, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Correction: Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Impact of PM2.5 exposure on gut microbiota abundance and composition in chronic disease patients - Yi-Hsueh Liu; Po Peng; Wei-Chun Hung; Ping-Hsun Wu; Chun-Chi Lu; Yi-Hsiung Lin; Chih-Da Wu; Chao-Hung Kuo; Szu-Chia Chen (Air Quality, Atmosphere & Health, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Active site-rich MIL-101(Fe) derived P-doped iron sulfide/carbon octahedra for oxygen evolution electrocatalysis - Ying-Jun Jhang Jian; Pin-Yan Lee; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Kevin C.-W. Wu; Kuo-Chuan Ho (Journal of Environmental Chemical Engineering, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Molecular Understanding of Cryopreservation of Marine Invertebrates: Achievements and New Perspectives - Federica Buttari; Sujune Tsai; Preeyanuch Thongpoo; Zhi-Hong Wen; Fu-Wen Kuo; Chiahsin Lin (Cell Biochemistry and Biophysics, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Multifunctional chitosan/polyvinyl alcohol film enhanced with N-TiO2 and jaboticaba peel extract for shrimp freshness monitoring and banana preservation - Girma Sisay Wolde; Chih-Huang Weng; Ying-Chen Chen; Shang-Ming Huang; Jenn-Wen Huang; Chanat Chokejaroenrat; Dong-Hau Kuo; Yao-Tung Lin (Food Packaging and Shelf Life, 2026)

Smart SERS platform with a machine-learning approach for the detection of thiram in fruit juices using an Ag NPs/NiFeLDH/MXene composite - Nazar Riswana Barveen; Petchi Raman Mariappan; Sathishkumar Chinnapaiyan; Yen-Yu Lin; Chih-Yu Kuo; Yu-Wei Cheng (Chemical Engineering Journal, 2026)

Optimizing Light Quality to Enhance Morphological and Physiological Responses in Japonica and Indica Rice Seedlings - Yun-Wei Kuo; Kuan-Hung Lin; Yi-Zhang Chen; Yue-Cing Su; Hsin-Hung Lin (Journal of Plant Growth Regulation, 2026)

Biomass-derived activated carbon-supported CuZnOS bimetallic oxysulfide catalyst with highly efficient catalytic reduction of organic and hexavalent chromium pollutants - Jiqing Li; Yuanbo Guo; Kening Xiang; Haoyu Wang; Tao Liu; Cuizhu Li; Zhenjie Wu; Yuhao Hong; Dong-Hau Kuo; Dongfang Lu; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2025)

Tailoring nickel glycerate electrodes through precursor chemistry and sulfurization for enhanced battery-supercapacitor hybrid performance - Tsung-Rong Kuo; Yun-Hsi Wang; Bo-Yang Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

ConSeisDiff: A conditional diffusion approach to mitigate synthetic-real disparities in seismic fault detection - Isack Farady; Chia-Chen Kuo; Soufiene Sellami; Chih-Yang Lin (Journal of Applied Geophysics, 2025)

Integrated metabolomics reveals immunomodulatory compounds in giant African snail (Achatina fulica) extracts for the giant river prawn (Macrobrachium rosenbergii) - Youshang Lin; Chen-Hsun Liu; Chiu-Hui Kuo; Bonien Chen; Wei-Ming Wu; Tsung-Meng Wu; Te-Yu Liao; Kuohsun Chiu (Fish & Shellfish Immunology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Trans-anethole enhances mesenchymal stem cell derived exosomes function to inhibit H2O2-induced rheumatoid arthritis-like inflammation in HIG-82 synovial cells - Tai-Lung Huang; Yu-Chun Chang; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Kuan-Ho Lin; Tsung-Jung Ho; Chih-Yang Huang (Molecular Biology Reports, 2025)

Streptococcal pyrogenic exotoxin a induces regulatory T cells via TNF-α-TNFR2 signaling - Chun-Hao Lu; Jason Ma; Ming-Chieh Lin; Cheng-Jang Wu; Chieh-Ying Kuo; Chuan Chiang-Ni; Ming-Ling Kuo (Medical Microbiology and Immunology, 2025)

Reframing construction labor for sustainable urban land transformation - Lin Liu; Hsing-Wei Tai; Tsung-Chun Chen; Kuo-Tai Cheng (Environment, Development and Sustainability, 2025)

Using an acidic vesicle tracer to identify potential bacterivores in coastal waters of the subtropical Western Pacific Ocean - Yun-Chi Lin; Yu-Chen Lin; Kuo-Ping Chiang; Chien-Pang Chin; Wen-Chen Chou (Frontiers in Marine Science, 2025)
Bacterivores play a key role in transferring energy through microbial food webs and are broadly classified as heterotrophic or mixotrophic based on the presence of inherent chloroplasts. Mixotrophs, especially in low-latitude regions, have recently gained attention due to their dual roles as primary producers and bacterial grazers, which enable them to thrive in nutrient-poor, stratified waters where traditional autotrophs or heterotrophs may be less competitive. This study investigated the composition of bacterivores in the coastal waters of northeastern Taiwan during the warm season (July and August 2022). A combination of LysoTracker staining, flow cytometry sorting, and 18S rRNA gene amplicon sequencing was used to rapidly identify heterotrophic and mixotrophic nanoflagellates (HNFs and MNFs, respectively) based on chloroplast autofluorescence. The dominant eukaryotic lineages included Alveolata, Stramenopiles, Opisthokonta, Chlorophyta, and Rhizaria. HNFs were primarily composed of MAST clades, choanoflagellates (Opisthokonta), Telonemia, and Radiolaria, while MNFs included cryptophytes, haptophytes, and chlorophytes such as Mamiella , Mantoniella and Tetraselmis , as well as stramenopiles like Dictyochophyceae and Chrysophyceae. Notably, several non-motile chlorophytes, including Chloropicon and members of Pycnococcaceae, were identified as potential bacterivores based on Lysotracker signals; however, their phagotrophic capability requires further confirmation in future studies. Despite the limitations of LysoTracker-based methods, this study reveals previously overlooked mixotrophic diversity and highlights the need for further validation. These findings advance our understanding of carbon flow and microbial dynamics in subtropical marine ecosystems under changing environmental conditions.

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Distribution and Property Prediction of Microplastics in Landfill Leachate under Different Treatment Processes Using Knowledge Graph-Enhanced Molecular Contrastive Learning - Meilan Zhang; Xuwei Zhao; Jia-hong Kuo; Xiaochuan Chen; Youcai Zhao; Kunsen Lin; Xuefei Zhou (Water Research, 2025)

Analytical framework for fast identification of hydrogeological boundaries and aquifer parameters in confined aquifers - Fu-Kuo Huang; Ying-Fan Lin; Hund-Der Yeh; Grace S. Wang (Journal of Hydrology, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Tyramine injection enhances immune function and disease resistance in Penaeus monodon - Wan-Lin Tsai; Li-Yang Hsu; Cheng-Ying Li; Hsin-Wei Kuo; Winton Cheng (Fish & Shellfish Immunology, 2025)

Development of cyclic double virtual phase model for advanced packed bed solar-driven thermo-chemical reactor - Hongyang Zuo; Qingyang Zhang; Kuo Zeng; Meng Lin; Ange Nzihou; Haiping Yang; Hanping Chen (Chemical Engineering Journal, 2025)

Thermal runaway dynamics of LFP batteries in confined pressurized atmospheres: From triggering to gas evolution - Lin Yu; Yuhui Wang; Qing Wang; Kuo Wang; Jianqi Zhang; Xinming Qian (Chemical Engineering Journal, 2025)

Fermented Soybean Pulp Alleviates Disease Progression of 5×FAD Model Mice - Chun-Yen Yang; Yu-Hsuan Liu; Ta-Chun Lin; Kuo-Hsuan Chang; Hsiu Mei Hsieh-Li (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder of the central nervous system, characterized by memory loss and cognitive decline. The two main hypotheses regarding AD involve the accumulation of amyloid-β (Aβ) forming plaques and the intracellular hyperphosphorylation of tau protein, leading to the formation of neurofibrillary tangles (NFT). These processes are accompanied by neuroinflammation and oxidative stress, and eventual neuronal death. While soy foods are widely recognized for their nutritional benefits, soybean pulp (okara), the residue left over from making tofu or soybean milk, is mostly discarded as kitchen waste, despite being rich in nutrients such as dietary fiber, protein, and isoflavones. This underutilized byproduct may serve as a valuable resource for functional food development and sustainable resource use. In this study, fermented soybean pulp (FS) demonstrated neuroprotective effects. In vitro, FS at concentrations of 0.001 µg/mL and 0.01 µg/mL significantly improved cell viability in Aβ-induced HT-22 cells and reduced lipid peroxidation. Further, in vivo oral administration of FS attenuated the cognitive deficits of 5 × FAD mice, enhancing both short and long-term memory and reducing anxiety-like behaviors. Immunohistochemical analysis revealed that the FS-treated 5 × FAD mice group significantly reduced hippocampal amyloid plaque accumulation and gliosis. FS also upregulated the expression levels of brain-derived neurotrophic factor (BDNF), PSD95, and synaptophysin, while preventing hippocampal neuronal loss. Mechanistically, FS may activate the Nrf2 antioxidant pathway and NF-κB-mediated inflammation through the modulation of the Akt/GSK3β signaling axis in the hippocampus. These molecular actions likely contribute to increased antioxidant enzymes and suppressed neuroinflammatory responses. Overall, this study suggests that FS has therapeutic potential for alleviating cognitive and behavioral impairments in AD. Moreover, the repurposing of soybean pulp, which would otherwise be discarded, enhances its utilization value and supports sustainable green recycling.

Three-dimensional material point analysis of the Guanghua landslide influenced by topographic constraints - Yi-Pin Peng; Kuo-Hsin Yang; Wei-Lin Lee; Tatag Yufitra Rus; Shih-Hao Cheng; Jyun-Yen Wang; Chihping Kuo (Landslides, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Optimization formulation of Rhodiola rosea L. nanoemulsion containing natural oil using response surface method (RSM): preparation, characterization, stability test and antioxidant activity - Benni Iskandar; Hsiu-Mei Lin; Ching-Kuo Lee (Phytochemistry Letters, 2025)

Anti-cancer effect of Willughbeia edulis Roxb. Stem extract in hepatocellular carcinoma cells through triggering apoptosis and G2/M cell cycle arrest - Thi Tuyet Nhung Nguyen; Yu-Chi Lin; Ching-Kuo Lee; Jing-Jy Cheng (Phytochemistry Letters, 2025)

Fabrication of superwetting gelatin/phytic acid/cellulose composites with antibacterial characteristics for separating complex contaminants from wastewater - Guyita Berako Belachew; Chien-Chieh Hu; Chih-Feng Wang; Mei-Yi Liao; Wei-Song Hung; Ching-Hsuan Lin; Shiao-Wei Kuo; Juin-Yih Lai (Journal of Water Process Engineering, 2025)

Oxygen-doped Ag3SbS3 with the hydrophobic-to-hydrophilic transformation for efficient reduction of organic and hexavalent chromium pollutants - Kening Xiang; Haoyu Wang; Tao Liu; Cuizhu Li; Zhengjie Su; Pengkun Zhang; Dong-Hau Kuo; Samuel Ndaghiya Adawara; Dongfang Lu; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2025)

Investigation of physical mechanisms behind full-scale engineered barrier systems through coupled thermal-hydraulic-mechanical (THM) simulations - Chia-Wei Kuo; Wan-Jung Kuo; Chung-Yi Lin (International Journal of Rock Mechanics and Mining Sciences, 2025)

A generalized chemical kinetics explains heterocyclic amine formation in high-temperature processed meats - Kuen-Yuh Wu; Yu-Hsuan Kuo; Pei-Chen Chao; Yu-Syuan Luo; Wan-Yu Lin; Su-Yin Chiang (Food Chemistry, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Photoresponsive azobenzene-grafted thermoplastic elastomers with controlled hard segment ratios for fast-rewritable and tunable surface relief gratings - Ming-Chieh Lin; Wen-Kai Cheng; Mohamed Gamal Mohamed; Wei-Hung Su; Shiao-Wei Kuo (Chemical Engineering Journal, 2025)

S-scheme heterojunction of N‐carbon dots/g-C3N4/MIL-101(Fe) photocatalytic membrane for peroxymonosulfate-activated photodegradation of enrofloxacin - Zhi-Fu Lin; Cheng-Kuo Tsai; YenJung Sean Lai; Thanh-Binh Nguyen; Prashanth Venkatesan; Ruey-An Doong (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

Enhancing arcade detection using bi-directed scene graphs with graph convolutional networks on street view imagery - Yi-Wen Mo; Chiao-Ling Kuo; Zhi-Sheng Lin (Remote Sensing Applications: Society and Environment, 2025)

A Deep-Sea probiotic platform: Dual-function biopreservation for aquaculture immunomodulation and meat shelf-life extension - Abhishek Negi; Bal Govind Yadav; Aakanksha; Chia-Wei Kuo; Prakash Kishore Hazam; Wen-Chun Lin; Ooi-Kock Teh; Jyh-Yih Chen (Innovative Food Science & Emerging Technologies, 2025)

Disruption of MRSA Biofilm and Virulence by Deep-Sea Probiotics: Impacts on Energy metabolism and Host Antimicrobial Peptides - Abhishek Negi; Chia-Wei Kuo; Prakash Kishore Hazam; Jih-Chao Yeh; Wen-Chun Lin; Yuan-Chao Lou; Chao-Yuan Yu; Tsai-Luen Yu; Tsai-Ming Lu; Jyh-Yih Chen (Probiotics and Antimicrobial Proteins, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Co-circulation of lineage 1 and lineage 3 porcine reproductive and respiratory syndrome virus type 2 (PRRSV-2) in Taiwan during 2018–2024 - Kun-Lin Kuo; Wei-Hao Lin; Ming-Tang Chiou; Jianqiang Zhang; Chao-Nan Lin (Veterinary Microbiology, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Reconstructed vanadium carbide MXene supported cerium based trimetallic phosphide as an efficient electrocatalyst for alkaline water splitting - Yu-Han Pan; Sakthivel Perumal; Mani Sakthivel; Shan-Ni Lin; Min-Hsin Yeh; Wen-Yueh Yu; Kuo-Chuan Ho (Chemical Engineering Journal, 2025)

Refining satellite-based HCHO/NO₂ diagnostics by isolating secondary HCHO: Enhanced mapping of ozone formation sensitivity - Kuo-En Chang; Tzu-Chi Lin; Ta-Chih Hsiao; Jia-Xian Lin; Tang-Huang Lin (Science of The Total Environment, 2025)

Fe/S co-doped BiOCl sulfur-oxychloride for efficient catalytic reduction of organic and Cr6+: Synergistic regulation of heterovalent states and oxygen vacancy defects - Cuizhu Li; Haoyu Wang; Tao Liu; Pengkun Zhang; Qiong Li; Kening Xiang; Dong-Hau Kuo; Dongfang Lu; Mengistu Tadesse Mosisa; Yiqiang Liao; Jinguo Lin; Xiaoyun Chen (Journal of Water Process Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Spatial patterns of essential fish habitats in the western Taiwan coast - Yu-Jia Lin; Chien-Cheng Lai; Hsu-Sen Chen; Tsu-Chun Chen; Kuo-Shu Chen; Norhafiz Hanafi; Pei-Jie Meng; Ying-Chin Fang; Chiee-Young Chen; Hsin-Ming Yen; Meng-Hsien Chen (Estuarine, Coastal and Shelf Science, 2025)

Dynamic weather-based scheduling for achieving energy savings in factories - Kung-Yueh Camyale Chao; Yi-Ting Liu; Chia-Yi Lee; Ji-Hong Lin; Chia-Ping Cheng; Ming-Hao Lee; Hung-Chi Kuo; Tai-Jen George Chen (Energy and Buildings, 2025)

Synergistic effects of heterovalent states, oxygen vacancy defects, and surface wettability engineering in S-doped AgBi(MoO4)2 for photocatalytic hydrogen evolution - Baoqian Yang; Xinru Wu; Benjamin Kunkadma Inusa; Dong-Hau Kuo; Pengkun Zhang; Cuizhu Li; Tao Liu; Dongfang Lu; Zhanhui Yuan; Jinguo Lin; Xiaoyun Chen (Chemical Engineering Journal, 2025)

GLA deficiency causes cardiac hypertrophy via enhanced autophagy - Wei Ou; Xi Li; Kuo Tang; Lin Ding; Tingting Sun; Qian Li; Tao Li (Science China Life Sciences, 2025)

The influence of shading facilities on outdoor thermal comfort, pedestrian walking speed, and indoor satisfaction - Zi-En Lin; Shiang-Yu Wang; Kuo-An Hung; Chiao-Jou Hsieh; Tzu-Ping Lin (International Journal of Biometeorology, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Tidal signal propagation in coastal aquifers considering semi-permeable boundaries and partial penetration effects - Fu-Kuo Huang; Ying-Fan Lin; Grace S. Wang; Barret L. Kurylyk (Journal of Hydrology, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

From colonization to spatial structuring: tracing invasion dynamics and natal origins using isoscapes in a non-native salmon - Esteban Avigliano; Ming-Tsung Chung; Nahuel Schenone; Rodrigo Clarke; Silvina Sturzenbaum; Ai-Lin Chen; Kuo-Fang Huang; Mathieu Leisen; Camille Duquenoy; Boris Diaz (Biological Invasions, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Mn/S co-doped BiOCl regulated with a hydrophobic-to-superhydrophilic transition and oxygen-vacancy defects for assisting photocatalytic hydrogen evolution - Zhengjie Su; Binghong Wu; Cuizhu Li; Dong-Hau Kuo; Pengkun Zhang; Longyan Chen; Dongfang Lu; Jinguo Lin; Xiaoyun Chen; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Toward Sustainable Fisheries: Lessons Learnt from Taiwan’s Offshore and Coastal Fishery Policy - Kuo-Huan Ting; Hao-Tang Jhan; Chih-Cheng Lin; Wen-Hong Liu (Coastal Management, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Application of high-hydrostatic pressure to extend shelf life of miso-marinated escolar loins during cold storage - Pi-Chen Wei; Chung-Saint Lin; Yi-Chen Lee; Chi Kang; Chia-Hung Kuo; Todd Hsu; Yung-Hsiang Tsai (Food Control, 2025)

Dexlansoprazole is an aryl hydrocarbon receptor agonist - Kuo-Liang Wei; Shan-Chun Chen; Chih-Yi Lin; Yu-Ting Chou; Wei-Tin Kuo; Teik-Wei Chuah; Jyan-Gwo Joseph Su (Food and Chemical Toxicology, 2025)

A novel MOF-on-MOF-derived carbon-encapsulated CeO2/Co/Co3O4 humidity-resistant heterojunction with abundant oxygen vacancies for efficient ozone removal - Abiyu Kerebo Berekute; An-Yu Wang; Kun-Yi Lin; Sepridawati Siregar; Kuo-Pin Yu (Environmental Research, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

Seasonality and extreme flooding can override the effects of debris dam removal on riverine species: a case study of macroinvertebrates - Tsung-Tse Hsieh; Jia-Yi Li; Che-Chang Lin; Mei-Hwa Kuo; Ming-Chih Chiu (Aquatic Ecology, 2025)

Ternary-heterojunction In2S3/Bi2S3/BiOBr catalyst with interfacial effect to enhance the photocatalytic degradation of organic dyes - Mengistu Tadesse Mosisa; Binghong Wu; Longyan Chen; Zhengjie Su; Pengkun Zhang; Adugna Boke Abdeta; Andualem Merga Tullu; Dong-Hau Kuo; Jinguo Lin; Xiaoyun Chen (Journal of Water Process Engineering, 2025)

Research on the explosive characteristics and suppression mechanisms of gas generation during thermal runaway of batteries in a charged state - Jianqi Zhang; Fangzhou Li; Lin Yu; Yuhui Wang; Kuo Wang; Chongye Chang; Minghui Li; Wenhao Hao; Xinming Qian (Chemical Engineering Journal, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Unraveling the heterogeneous hydrogeological characteristics in the Choushui River alluvial fan, Taiwan, through observations from the multi-layer compaction monitoring wells - Reyhan Azeriansyah; Kuo-En Ching; Cheng-Wei Lin; Kuo-Chin Hsu; Pei-Ching Tsai; Chao-Lung Yeh; Ruey-Juin Rau (Engineering Geology, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

A flame-retardant and weakly solvated gel electrolyte for high-performance and high-safety Ah class sodium-ion batteries - Lixing Xue; Hongyan Pan; Yuejun Wang; Zhengyi Wang; Xuhui Wang; Qian Lin; Kuo Zhang; Xiangnan Bu; Maohui Bai; Bo Hong (Chemical Engineering Journal, 2025)

Epigenetic Modifications as Novel Therapeutic Strategies of Cancer Chemoprevention by Phytochemicals - Hui-Hsia Hsieh; Min-Zhan Kuo; I-An Chen; Chien-Ju Lin; Victor Hsu; Wei-Chun HuangFu; Tien-Yuan Wu (Pharmaceutical Research, 2025)

Regional sea level budget around Taiwan and Philippines over 2002‒2021 inferred from GRACE, altimetry, and in-situ hydrographic data - Wen-Hau Lan; Chi-Ming Lee; Chung-Yen Kuo; Li-Ching Lin; Eko Yuli Handoko (Journal of Geodesy, 2025)
The regional sea level budget and interannual sea level changes around Taiwan and Philippines are studied using altimetry, GRACE, and in-situ hydrographic data during 1993‒2021. Results show that the average sea level trend around Taiwan and Philippines during 1993–2021 derived from the altimetric data is 3.6 ± 0.2 mm/yr. Over 2002–2021, the study shows closure of sea level budget in the eastern ocean of Taiwan and Philippines within the observed data uncertainties, and the ocean mass accounts for 88%–100% of the observed sea level rise. In contrast, the sea level budget is not closed in the western ocean of Taiwan and Philippines, probably due to the lack of complete coverage by in-situ ocean observing systems. In addition, both regional sea level anomalies and their steric component around Taiwan and Philippines exhibit pronounced interannual and decadal variabilities. The trade wind stress associated with El Niño–Southern Oscillation and Pacific Decadal Oscillation offers a compelling explanation for the interannual and decadal signals of sea level anomalies in the southern ocean of Taiwan, with negative correlations of − 0.78 to − 0.64, indicating that trade wind stress makes a negative contribution to interannual-to-decadal sea level variability. In the northwestern ocean of Taiwan, the sea level variation is strongly influenced by the local monsoon system and shallow bathymetry with an annual amplitude of 90.3 ± 2.9 mm, larger than those in other regions around Taiwan and Philippines, where ocean mass is dominant with a high correlation with the sea level (+ 0.75 to + 0.78).

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

Potato Protein Hydrolysate (PPH902) treatment in adipocytes inhibits lipogenesis by activating AMPK - Yi-Ju Chen; Ching-Fang Chang; Rathinasamy Baskaran; Chih-Hung Liang; Hsin-Ning Kuo; Mosleh Mohammad Abomughaid; Wan-Teng Lin (South African Journal of Botany, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

How destination attributes affect mountain bikers’ behavioral intention: The mediating roles of enduring involvement and place attachment - Nien-Te Kuo; Lu-Ping Lin; Kuo-Chien Chang; Yi-Sung Cheng (Journal of Outdoor Recreation and Tourism, 2024)

Efficient fluoride recovery from wastewater using mesoporous Ca-based nanomaterials derived from municipal solid waste incineration fly ash via fluidized bed crystallization - Cheng-Kuo Tsai; Nur Atirah Afifah Sezali; Zhi-Fu Lin; Jao-Jia Horng; Hui Lin Ong (Journal of Environmental Chemical Engineering, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Seasonal distribution and population genetic structure of Psenopsis anomala (Japanese butterfish) inferred from otolith oxygen isotope ratios and mitochondrial DNA - Aafaq Nazir; Ting-Hung Lin; Tien-Hsia Kuo; Kotaro Shirai; Pei-Ling Wang; Jen-Chieh Shiao (Estuarine, Coastal and Shelf Science, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Hydrology controls sulfuric acid-mediated weathering in an orogenic regime of southwestern Taiwan - Hou-Chun Liu; Meng-Xuan Li; Chen-Feng You; Yan-Hong Chen; Kuo-Fang Huang; Chuan-Hsiung Chung; Guan-Wei Lin (Science of The Total Environment, 2024)

Mapping new psychoactive substances: Leveraging GIS technology for advanced global surveillance and policy support - Ting-Jung Ku; Tien-Chueh Kuo; Olivia A. Lin; Yufeng Jane Tseng (Regulatory Toxicology and Pharmacology, 2024)

High-contrast electrochromic coatings and devices for health assurance, visual comfort and energy-saving in buildings - Chung-Wen Kuo; Han-Yu Chen; Chen-Hao Yeh; Yuan-Chung Lin; Jeng-Kuei Chang; Pei-Ying Lee; Tzi-Yi Wu (Energy and Buildings, 2024)

The impact of social partners: investigating mixed-strain housing effects on aging in female mice - Chih-Lin Lee; Yu-Chiao Lin; Tsung-Han Kuo (Biogerontology, 2024)

Distributed dynamic event-triggered flocking control for multiple unmanned surface vehicles - Yong Hao; Kuo Hu; Lin Liu; Jixiang Li (Ocean Engineering, 2024)

Geochemical characteristics of peridotite xenoliths from the Vitim volcanic field: Insight to late Cenozoic mantle upwelling in SE Siberia - Yu-Hsiang Chien; Kuo-Lung Wang; Victor Kovach; Mikhail Kuzmin; Alexender Vorontsov; Alexei Ivanov; Kwan-Nang Pang; Yoshiyuki Iizuka; Hao-Yang Lee; Sun-Lin Chung; Der-Chuen Lee (Lithos, 2024)

Synthesis and characterization of Ce-BiOBr/Bi2S3 catalyst with enhanced catalytic activity for organic dye reduction under dark - Mengistu Tadesse Mosisa; Pengkun Zhang; Binghong Wu; Longyan Chen; Zhengjie Su; Ping Li; Hanya Zhang; Ambar Farooq; Ting Huang; Adugna Boke Abdeta; Osman Ahmed Zelekew; Dong-Hau Kuo; et al. (Journal of Environmental Chemical Engineering, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Elevated surface ozone concentration caused by subtropical cyclones and topographical effect: Model simulation and field measurement - Kuo-Cheng Lo; Wen-Hsi Cheng; Chitsan Lin; Chung-Hsuang Hung; Chung-Shin Yuan; Yu-Lun Tseng (Urban Climate, 2024)

Investigating the impact of ultrasound on the structural, physicochemical, and emulsifying characteristics of Dioscorin: Insights from experimental data and molecular dynamics simulation - Qi Gao; Yu-qi Yang; Hao-nan Nie; Bing-qing Wang; Xue Peng; Ning Wang; Jiang-kuo Li; Jia-jia Rao; You-lin Xue (Food Chemistry, 2024)

Synergistic vacancy defects and the surface hydrophobic-to-superhydrophilic wetting engineering in W/S co-doped BiOI for enhanced photocatalytic hydrogen evolution - Zhengjie Su; Chengning Ye; Yiyang Xu; Binghong Wu; Dong-Hau Kuo; Xinru Wu; Baoqian Yang; Pengkun Zhang; Longyan Chen; Dongfang Lu; Jinguo Lin; Zhanhui Yuan; et al. (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Surface ligand engineering of perovskite quantum dots for n-type and stretchable photosynaptic transistor with an ultralow energy consumption - Wei-Cheng Chen; Yan-Cheng Lin; Zih-Syuan Syu; Ya-Shuan Wu; Kai-Wei Lin; Cheng-Liang Liu; Chi-Ching Kuo; Wen-Chang Chen (Chemical Engineering Journal, 2024)

Improving Ampoule Opening Safety: An Exploratory Comparative Study on an Innovative Ampoule Opener - Zu-Chun Lin; Ming-Chuan Kuo; Hao-Wen Chang; Malcolm Koo (Journal of Pharmaceutical Innovation, 2024)

Inorganic and organic nutrients in tropical–subtropical Western Pacific coral reef waters - Huei-Ting Lin; Vianney Denis; Chih-Chiang Hsieh; Chieh-Jhen Chen; Wanchien Victoria Hsiao; Pei-Ling Wang; Chih-Chieh Su; Yan-Ning Kuo (Coral Reefs, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Feasibility studies in applying cork to pile-type two-layered seismic metamaterials - Tung-Yu Wu; Wei-Lin Teng; Hsiang-Hao Hsieh; Shiang-Jung Wang; Kuo-Chun Chang (Soil Dynamics and Earthquake Engineering, 2024)

Multifaceted leaf litter traits shape soil fauna communities: Evidence from subtropical monocultural plantations - Dangjun Wang; Wuyang Xie; Xiaoyuan Lin; Fan Li; Chaochao Deng; Xiangyu Zeng; Kuo Tan; Yiping Yuan; Zhirong Gu; Mingxi Jiang; Zhun Mao; Juan Zuo (Forest Ecology and Management, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Diversity and distribution of small-sized planktonic ciliate communities in the East China Sea - Wei-Ting Chen; Yun-Chi Lin; Sheng-Fang Tsai; Kuo-Ping Chiang (Frontiers in Marine Science, 2024)
Ciliates are an important ecological component in the microbial food web, but few studies have been conducted on the spatial distribution of small-sized planktonic ciliate communities in the East China Sea (ECS). Investigating ciliate communities using conventional morphological approaches is particularly difficult for the small, fragile, and naked species. Therefore, we applied DNA metabarcoding analysis to explore the spatial pattern of small-sized planktonic ciliate community structure within the surface, deep chlorophyll maximum (DCM), and bottom layers. Results showed the cosmopolitan species, Leegaardiella sp., was dominant and widespread in the ECS. The relative abundance of the mixotrophic family Tontonnidae decreased in the deeper layer. We characterized water masses of the ECS using environmental variables. In nano-sized ciliate communities, non-metric multidimensional scaling (NMDS) plots revealed a correlation with temperature, salinity, density, and depth. The circulation patterns were similar to cluster analysis results, suggesting that hydrographic conditions shaped small-sized ciliate community composition.

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Risk factors for mortality in Stenotrophomonas maltophilia bacteremia – a meta-analysis - Chienhsiu Huang; Lichen Lin; Sufang Kuo (Infectious Diseases, 2024)

3D-printed Al2O3 framework supported carbon-bridged tri-s-triazine of g-C3N4 for photocatalytic tetracycline oxidation - Chechia Hu; Lee-Lee Chang; Wei Chen; Wan-Yuan Hsu; Szu-Chia Chien; Chien-Hua Chen; Yu-Ting Lin; Tzu-Jung Hsu; Kuo-Lun Tung (Chemical Engineering Journal, 2024)

A modified lift-off test for restressing anchors of a rehabilitated landslide slope - Shih-Hao Cheng; Kuo-Hsin Yang; Shih-Yuan Lin; Chen-Kan Liao; Hung-Jiun Liao (Landslides, 2024)

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

A cost-effective approach to uncovering and mapping buildings’ exterior arcades using street view imagery - Chiao-Ling Kuo; Zhi-Sheng Lin (Remote Sensing Applications: Society and Environment, 2024)

A novel V/S co-doped BiOBr catalyst for high-efficiency catalytic reduction of toxic organic and hexavalent chromium pollutants under dark - Mengistu Tadesse Mosisa; Pengkun Zhang; Zhengjie Su; Binghong Wu; Longyan Chen; Yiqiang Liao; Ambar Farooq; Dongfang Lu; Adugna Boke Abdeta; Dong-Hau Kuo; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2024)

Impacts of ship emissions and sea-land breeze on urban air quality using chemical characterization, source contribution and dispersion model simulation of PM2.5 at Asian seaport - Yu-Lun Tseng; Wen-Hsi Cheng; Chung-Shin Yuan; Kuo-Cheng Lo; Chitsan Lin; Chia-Wei Lee; Gerry Bagtasa (Environmental Pollution, 2024)

A memory-rich conjugated microporous polymer-based electrochromic framework through two-in-one metal catalyst free route - Gaurav Kumar Silori; Szu-Chia Chien; Li-Chiang Lin; Kuo-Chuan Ho (Chemical Engineering Journal, 2024)

Different microbial communities in paddy soils under organic and nonorganic farming - Jimmy Kuo; Daniel Liu; Wei Hao Wen; Ching Yuan Chiu; Wanyu Chen; Yun Wen Wu; Fang-Ting Lai; Chorng-Horng Lin (Brazilian Journal of Microbiology, 2024)

Synergistic Co/S co-doped CeO2 sulfur-oxide catalyst for efficient catalytic reduction of toxic organics and heavy metal pollutants under dark conditions - Pengkun Zhang; Haoyu Wang; Yujie Lai; Yunzhuo Xu; Longyan Chen; Qinhan Wu; Dong-Hau Kuo; Dongfang Lu; Mengistu Tadesse Mosisa; Jiqing Li; Jinguo Lin; Xiaoyun Chen (Journal of Water Process Engineering, 2024)

Hydrazine-driven cation valence regulation and defect engineering in CeVO4 for highly efficient reduction of organic dyes and heavy metal pollutants in the dark - Pengkun Zhang; Yujie Lai; Xinghua Dai; Yunzhuo Xu; Xinru Wu; Baoqian Yang; Dong-Hau Kuo; Dongfang Lu; Qinhan Wu; Mengistu Tadesse Mosisa; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2024)

Dual-functional membranes of CQDs/TiO2 @PI/PES nanofibers for the high filter efficiency of ultrafine particles and photocatalytic activity - Hua-Wei Chen; Yu-Lin Kuo; Shu-Hsien Huang; Chyow-San Chiou; Ying-Cih Chen; Wei-Ting Chen (Journal of Environmental Chemical Engineering, 2024)

Evaluate the effect of β-cyclodextrin on the sensory and physicochemical properties of bitter gourd extract during thermal processing - Cam Thi Hong Tran; Hui-Min David Wang; Le Thi Hong Anh; Chitsan Lin; Chun-Yung Huang; Chia-Hung Kuo (Food Chemistry, 2024)

Ecological and functional differences of abundant and rare sub-communities in wastewater treatment plants across China - Kuo Yang; Wei Liu; Hui-min Lin; Tan Chen; Ting Yang; Bing Zhang; Xianghua Wen (Environmental Research, 2024)

Mechanochemical synthesis of Ni/MgO dual functional materials at room temperature for CO2 capture and methanation - Zhan-Kuo Guo; Su Gao; Shu-Xiang Xiang; Jin-Peng Wang; Guo-Cui Mao; Hui-Lin Jiang; Bao-Xia Dong; Yun-Lei Teng (Chemical Engineering Journal, 2024)

Breaking prolonged sitting increases 24-h physical activity and self-perceived energy levels but does not acutely affect cognition in healthy adults - Feng-Chih Kuo; Yun-Ting Lin; Ting-Yu Chueh; Yu-Kai Chang; Tsung-Min Hung; Yung-Chih Chen (European Journal of Applied Physiology, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Exploring the potential of the nano-based sunscreens and antioxidants for preventing and treating skin photoaging - Chih-Hung Lin; Ming-Hsien Lin; Yu-Kuo Chung; Ahmed Alalaiwe; Chi-Feng Hung; Jia-You Fang (Chemosphere, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

Genetic diversity and relatedness of feline parvovirus in Vietnam and its potential implications for canine-feline transmission - Hoang Minh; Nguyen Vu Son; Hoang Minh Duc; Chao-Nan Lin; Yu-Chung Tyan; Kuo-Pin Chuang (Archives of Virology, 2024)

The Role of the Cerebellum in Learning to Predict Reward: Evidence from Cerebellar Ataxia - Jonathan Nicholas; Christian Amlang; Chi-Ying R. Lin; Leila Montaser-Kouhsari; Natasha Desai; Ming-Kai Pan; Sheng-Han Kuo; Daphna Shohamy (The Cerebellum, 2023)

Review: Defense responses in sweetpotato (Ipomoea batatas L.) against biotic stress - Shi-Peng Chen; Yun-Wei Kuo; Jeng-Shane Lin (Plant Science, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Heterostructured YFeO3/CeO2 as efficient photoelectrode for photoelectrochemical degradation of organic pollutants under visible light irradiation - Yen-Shen Kuo; Mu-Jung Lin; Cheng-Liang Hsu; Yi-Hung Liu (Journal of Water Process Engineering, 2023)

Effects of vitamin D and zinc deficiency in acute and long COVID syndrome - Kuang-Yu Chen; Chin-Kuo Lin; Ning-Hung Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Feasibility of forecasting convective rain by diagnosing intracloud lightning jumps - Jyh-Huei Tai; Wei-Kuo Soong; Pei-Hua Tan; Mark Yin-Mao Wang; Po-Hsiung Lin (Meteorology and Atmospheric Physics, 2023)
This study conducted a comparison of the data quality of Earth Networks (EN) and Taiwan Power Company’s Total Lightning Detection System (TLDS) and evaluated the feasibility of using intracloud (IC) lightning to issue convective rain warnings. The results indicate uncertainties in the TLDS positioning of IC lightning. When forecasting convective rain on the basis of IC lightning jumps using EN data, the mean prefigurance and postagreement scores were 0.8 and 0.67, respectively, which were more favourable than the respective TLDS scores of 0.65 and 0.47. In regions with high TLDS positioning uncertainties, the use of EN data increased the number of prefigurance and postagreement hits in each analysis zone and raised the prefigurance and postagreement scores to 0.3 and 0.5, respectively. This indicates that analyses using EN data can reduce the risk of missed convective rain warnings when diagnosing IC jumps and can reduce the false alarm rate. In this study, IC jumps preceded convective rains by a maximum of 27.5–39.3 min on average in all analysis zones across Taiwan. The results suggest that diagnosing IC jumps to forecast convective rain is feasible, but until the uncertainties in the positioning of IC lightning using TLDSs have been remedied, EN data are the more suitable diagnostic choice.

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Association of mono-2-ethylhexyl phthalate with adverse outcomes in chronic hemodialysis patients - Chia-Lin Wu; Yu-Wei Fang; Yi-Chou Hou; Kuo-Cheng Lu; Wen-Hsin Tsai; Ping-Hsun Lu; Tzong-Shyuan Lee; Ko-Lin Kuo (Environmental Science and Pollution Research, 2023)
Phthalate exposure is widespread and has a global impact. Growing evidence shows that mono-2-ethylhexyl phthalate (MEHP) exposure has a negative impact on human health. However, whether MEHP exposure is associated with mortality and other adverse outcomes in hemodialysis patients remains unknown. This study prospectively enrolled 217 patients on maintenance hemodialysis from June 30, 2021, to August 16, 2022. Baseline serum MEHP, di-2-ethylhexyl phthalate (DEHP), and indoxyl sulfate (IS) concentrations were measured. Primary endpoints were all-cause mortality or composite adverse outcomes, including all-cause death plus hospitalization due to cardiovascular disease, heart failure, stroke, infection, or cancer. Serum MEHP concentrations were positively associated with DEHP but not indoxyl sulfate concentrations in hemodialysis patients. Additionally, serum MEHP concentrations were significantly and independently associated with all-cause mortality and composite adverse outcomes (adjusted hazard ratios [HRs], 1.04 and 1.03 per ng/mL, 95% confidence intervals [CIs], 1.01–1.07 and 1.00–1.05; p = 0.016 and 0.015, respectively). We found a cutoff value of MEHP for predicting both endpoints. Patients with serum MEHP concentrations of ≥ 41.8 ng/mL had much higher risks for all-cause mortality and composite adverse outcomes (adjusted HRs, 39.2 and 13; 95% CIs, 2.44–65.7 and 2.74–61.4; p = 0.011 and 0.001, respectively). MEHP exposure is significantly associated with higher risks for all-cause mortality and composite adverse outcomes. Hemodialysis patients with serum MEHP concentrations above 41.8 ng/mL had much poorer prognoses regarding both outcomes.

Environment-friendly organic coordination design of Z-scheme heterojunction N-BOB/BiOIO3 for efficient LED-light-driven photocatalytic and electrochemical performance - Yi-Lun Chen; Li Chen; Ming-Yen Sung; Jung-Hua Lin; Chao-Jan Liu; Chih-Jou Kuo; Er-Chieh Cho; Kuen-Chan Lee (Chemosphere, 2023)

All-in-one self-floating porous foams as robust heat-blocking layers for efficient photothermal conversion and solar desalination - Liping Ren; Wei Zhou; Lei Wang; Kuo Lin; Yachao Xu; Jiaxing Wu; Ying Xie; Honggang Fu (Science Bulletin, 2023)

Development of a sampling assembly for PM2.5 CEMS - Shibo Wang; Yu-Mei Kuo; Chih-Wei Lin; Sheng-Hsiu Huang; Chih-Chieh Chen (Journal of Aerosol Science, 2023)

Plasma-engineered graphene quantum dot-based nanocomposites as smart CO2-philic membranes with extremely high separation performance - Yi-Jui Yeh; Wei Lin; Wei-Hung Chiang; Kuo-Lun Tung (Chemical Engineering Journal, 2023)

Large-diameter trees buffer monsoonal changes to tree biomass over two decades - Chen-Chia Ku; Jianwu Tang; Wei-Chun Chao; Kuo-Jung Chao; Guo-Zhang Michael Song; Huan-Yu Lin; James A. Lutz (Plant Ecology, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Decreased levels of perfluoroalkyl substances in patients receiving hemodialysis treatment - Jih-Kai Huang; Yun-Shiuan Chuang; Ping-Hsun Wu; Chi-Jung Tai; Jye-Ru Lin; Mei-Chuan Kuo; Yi-Wen Chiu; Ping-Chi Hsu; Ming-Tsang Wu; Samira Salihovic; Yi-Ting Lin (Science of The Total Environment, 2023)

Co/S co-doped Mn3O4-based sulfur-oxide nano-flakes catalyst for highly efficient catalytic reduction of organics and hexavalent chromium pollutants - Longyan Chen; Zhengjie Su; Qinhan Wu; Dong-Hau Kuo; Adugna Boke Abdeta; Binghong Wu; Pengkun Zhang; Mengistu Tadesse Mosisa; Osman Ahmed Zelekew; Jinguo Lin; Xiaoyun Chen; Xueshen Liu (Journal of Water Process Engineering, 2023)

Sulfur-doped Sb4Mo10O31 bimetallic sulfur-oxide catalyst for highly efficient reduction of toxic organic and hexavalent chromium under dark - Ping Li; Qinhan Wu; Qiao Ji; Adugna Boke Abdeta; Dong-Hau Kuo; Ting Huang; Hanya Zhang; Osman Ahmed Zelekew; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2023)

Flash-ignition of carbon black synthesized from acetylene diffusion flames and its application as ignition agents - Chih-Yung Wu; Yi-Chu Chen; Tse-Hao Wang; Po-Han Lin; Yi-Kuan Kuo (Fuel, 2023)

The role of the core microorganisms in the microbial interactions in activated sludge - Huimin Lin; Yichen Zheng; Yuankai Yang; Fengyi Liu; Kuo Yang; Bing Zhang; Xianghua Wen (Environmental Research, 2023)

Novel visible-light-active P-g-CN-based α-Bi2O3/WO3 ternary photocatalysts with a dual Z-scheme heterostructure for the efficient decomposition of refractory ultraviolet filters and environmental hormones: Benzophenones - Abiyu Kerebo Berekute; Kuo-Pin Yu; Yi-Hsueh Brad Chuang; Kun-Yi Andrew Lin (Environmental Research, 2023)

Neuroprotective Effects of Probiotic Lactobacillus reuteri GMNL-263 in the Hippocampus of Streptozotocin-Induced Diabetic Rats - Jing-Ying Lin; Bruce Chi-Kang Tsai; Hui-Chuan Kao; Chien-Yi Chiang; Yun-An Chen; William Shao-Tsu Chen; Tsung-Jung Ho; Chun-Hsu Yao; Wei-Wen Kuo; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2023)

New depth record for oval squid, Sepioteuthis lessoniana, egg capsules in a mesophotic coral ecosystem natural habitat - Chao-Yang Kuo; Chun-Yen Lin; Ming-Jay Ho; Chaolun Allen Chen (Marine Biodiversity, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

University-driven coastal partnerships to address ghost gear pollution: A case study in Penghu Islands of Taiwan - Chih-Cheng Lin; Kuo-Huan Ting; Hao-Tang Jhan; Chung-Lun Liu; Li-Shu Chen; Wen-Hong Liu (Marine Policy, 2023)

Revealing the mechanism underlying the effects of γ-aminobutyric acid-dioscorin interactions on dioscorin structure and emulsifying properties by molecular dynamic simulations - Yun-long Chen; Hao-nan Nie; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Xueling Chen; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Research International, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Fast-eroding Taiwan and transfer of orogenic sediment to forearc basins and trenches in the Philippine and South China seas - Eduardo Garzanti; Kalyani Nayak; Marta Padoan; Giovanni Vezzoli; Alberto Resentini; Sebastien Castelltort; Andrew Tien-Shun Lin; Nathalie Babonneau; Gueorgui Ratzov; Shu-Kun Hsu; Kuo-Fang Huang (Earth-Science Reviews, 2023)

Applying an air curtain to reduce surgical smoke concentration - Xuan-Huy Ninh; Hung-Yu Tzeng; Tak-Wah Wong; Yu-Ting Wu; Yao-Lung Kuo; Ming-Yeng Lin (Air Quality, Atmosphere & Health, 2023)

Adsorption and desorption characteristics of heavy metals onto conventional and biodegradable plastics - Wei-Hong Lin; Hsi-Yen Wang; Jeff Kuo; Shang-Lien Lo (Chemosphere, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

A novel framework for spatiotemporal groundwater pumping process estimation based on data-driven approaches - Hwa-Lung Yu; Hua-Ting Tseng; Ying-Fan Lin; Chun-Hung Chen; Ying-Chang Kuo; Yun-Ta Cheng (Journal of Hydrology, 2023)

Arsenic exposure associated with lung interstitial changes in non-smoking individuals living near a petrochemical complex: A repeated cross-sectional study - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Hung-Hsun Lin; Huang‐Chi Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Pollution, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Occurrences of similar viral diversity in campus wastewater and reclaimed water of a university dormitory - Hsion-Wen David Kuo; Diaiti Zure; Chih-Rong Lin (Chemosphere, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Development of a high-fidelity failure prediction system for reinforced concrete bridge columns using generative adversarial networks - Ting-Yan Wu; Rih-Teng Wu; Ping-Hsiung Wang; Tzu-Kang Lin; Kuo-Chun Chang (Engineering Structures, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Comparative Life Cycle Assessment (LCA) on battery electric and combustion engine motorcycles in Taiwan - Falk Schneider; Daniel Sebastián Castillo Castro; Kuo-Che Weng; Cheng-Hsiang Shei; Hsin-Tien Lin (Journal of Cleaner Production, 2023)

Activation of Cu3(MoO4)2(OH)2 with the hydrazine-driven cation reduction into a highly efficient catalyst for the reduction of organic dyes and heavy metals ion - Qinhan Wu; Pengkun Zhang; Dong-Hau Kuo; Binghong Wu; Adugna Boke Abdeta; Zhengjie Su; Longyan Chen; Osman Ahmed Zelekew; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Characterization of VOCs during diesel oil composting process - Tachen Lin; Shulung Kuo; Adnan Hussain; Zhigui Chen; Manlin Huang; Chitsan Lin (Bioresource Technology Reports, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Blood lead (Pb) is associated with lung fibrotic changes in non-smokers living in the vicinity of petrochemical complex: a population-based study - Wei-Hoong Yau; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Chih-Wen Wang; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

Outcomes between endoscopic-assisted minimally invasive surgery and conventional craniotomy in spontaneous intracerebral hemorrhage - Yi-Ying Hsieh; Bo-An Chen; Kuan-Hao Fu; Yi-Hsien Kuo; Ying-Yun Chen; Jiun-Lin Yan; Pin-Yuan Chen (Neurophysiology, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Screening of marine Actinomycetia with bioactive metabolites from nearshore and deep sea marine sediments in southwestern Taiwan - Jimmy Kuo; Kuan-Ting Chen; Mei-Chin Lu; Ping-Jung Sung; Chorng-Horng Lin; Yung-Sen Huang (Biologia, 2023)

Embedded information of aerosol type, hygroscopicity and scattering enhancement factor revealed by the relationship between PM2.5 and aerosol optical depth - Kuo-En Chang; Ta-Chih Hsiao; Si-Chee Tsay; Tang-Huang Lin; Stephen M. Griffith; Chian-Yi Liu; Charles C.-K. Chou (Science of The Total Environment, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

Elevated temperature affects energy metabolism and behavior of bumblebees - Yun Kuo; Yun-Heng Lu; Yu-Hsien Lin; Yu-Chun Lin; Yueh-Lung Wu (Insect Biochemistry and Molecular Biology, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

Juvenile and Trash Fish Excluder Device (JTED) for Taiwanese Bottom Trawl - Chao-Ching Chen; Hsin-Zong Lin; Kuo-Wei Lan (Fishes, 2023)
Juvenile and trash fish excluder devices (JTEDs) are used to mitigate the ecological impact of trawling. Trawling has a large ecological footprint in Taiwan. Thus, this study designed three JTEDs, which differed only in grid interval, for single boat bottom otter trawls that are commonly used in Taiwan. The designed JTEDs were tested in the waters off of Kaohsiung on a Kaohsiung-based bottom trawler, and the results were as follows. (1) At least 300 species were caught, and 189 of these species had little commercial value; their weight accounted for 52.5% of the total catch. (2) The three JTEDs had good exclusion performance. (3) The ratios of the weight of bycatch excluded to the weight of total catch were 7.9%, 29.1%, and 36.2%, for grid intervals of 10, 15, and 20 mm, respectively. (4) JTEDs with grid intervals of 10, 15, and 20 mm were associated with a 0.4%, 11.5%, and 19.0% loss in revenue, respectively. (5) Mature (and thus commercially valuable) Loliginidae tended to be excluded when the grid interval was 20 or (especially) 15 mm. In general, the designed JTEDs should be used at a grid size of 15 mm because this strikes the best balance between profitability and sustainability.

Challenges to govern a global sustainability science problem: Lessons from a domestic climate change research project - Shih-Yun Kuo; Tsung-Ta Tang; Huang-Hsiung Hsu; Lee-Yaw Lin; Yung-Ming Chen (Environment, Development and Sustainability, 2023)

Agglomeration-influenced transformation of heavy metals in gas-solid phases during simulated sewage sludge co-incineration: Effects of phosphorus and operating temperature - Kunsen Lin; Youcai Zhao; Jia-Hong Kuo; Chiou-Liang Lin (Science of The Total Environment, 2023)

Layered fully distributed formation-containment tracking control for multiple unmanned surface vehicles - Yong Hao; Zhixian Lin; Kuo Hu; Lin Liu (Ocean Engineering, 2023)

Seasonality can override the effects of anthropogenic activities on microplastic presence in invertebrate deposit feeders in an urban river system - Chun-Ting Lin; Ming-Chih Chiu; Mei-Hwa Kuo (Journal of Hazardous Materials, 2023)

Data‐driven models employed to waste plastic in China: Generation, classification, and environmental assessment - Kunsen Lin; Youcai Zhao; Meilan Zhang; Wenjie Shi; Jia‐Hong Kuo (Journal of Industrial Ecology, 2023)
It is crucial to precisely predict the generation of plastic waste and realize its fine classification in terms of policy demand and environmental benefits. Only a few studies have used the date‐driven model to forecast the amount of plastic waste. The benefits of classifying the plastic waste using deep learning have also been only scarcely reported in the literature. Therefore, this study used the Prophet model to estimate the amount of plastic waste from 2005 to 2025. Four types of Visual Geometry Group Networks based on Transfer Learning (TLVGGNet) were performed for classifying the plastic waste. Potentials of saved energy, the reduction of green‐house gases emission (GHG), and air pollutants were also discussed under different scenarios (current recycling system and TLVGGNet system). The results showed that the amount of waste plastic was anticipated to be 26.44 Mt in 2020 and 33.18 Mt in 2025 in China. The method of transfer learning could shorten the training time and improve the performance of the TLVGGNet‐11 model in the test dataset (41.6–68.1%). Moreover, TLVGGNet‐16 was considered to be the most optimum model for plastic waste classification in terms of training time (83.94 s), accuracy (75.5%), precision (76.9%), recall (75.5%), and F1 score (75.1%). The TLVGGNet‐16 system contributes about 12.15–15.97% in terms of electricity‐savings. Compared with the current recycling system, the amount of CO 2 emissions saved and reduction in CH 4 emissions could be more than 8–10% and 0.4–0.5%, respectively, in the TLVGGNet‐16 system. The saved VOC S and NO X emissions were within the ranges of 34.84–127.22 billion kg and 93.64–414.14 billion kg between 2017 and 2025 using the method of deep learning.

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Wild coral oocytes are more amenable to low temperature preservation than cultured counterparts - Chiahsin Lin; Cheng-Chia Lin; Fu-Wen Kuo; Sujune Tsai (Marine Environmental Research, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

Angelica dahurica attenuates melanogenesis in B16F0 cells by repressing Wnt/β-catenin signaling - Chien-Liang Fang; Debakshee Goswami; Chia-Hua Kuo; Cecilia Hsuan Day; Mei-Yi Lin; Tsung-Jung Ho; Liang-Yo Yang; Dennis Jine-Yuan Hsieh; Tzu-Kai Lin; Chih-Yang Huang (Molecular & Cellular Toxicology, 2023)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

How can sports entrepreneurs achieve their corporate sustainable development goals under the COVID-19 epidemic? - Kuo Chiang Ting; Hsiao-Hsien Lin; Jung-Hul Chien; Kuan-Chieh Tseng; Chin-Hsien Hsu (Environmental Science and Pollution Research, 2022)

Modeling of rupture using strong motion generation area: a case study of Hualien earthquake (Mw 6.1) occurred on April 18, 2019 - Saurabh Sharma; Anand Joshi; Sandeep; Che-Min Lin; Chun-Hsiang Kuo; Kuo-Liang Wen; Sandeep Singh; Mukat Lal Sharma; Mohit Pandey; Jyoti Singh (Acta Geophysica, 2022)

Physiological Recordings of the Cerebellum in Movement Disorders - Ami Kumar; Chih-Chun Lin; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)
The cerebellum plays an important role in movement disorders, specifically in symptoms of ataxia, tremor, and dystonia. Understanding the physiological signals of the cerebellum contributes to insights into the pathophysiology of these movement disorders and holds promise in advancing therapeutic development. Non-invasive techniques such as electroencephalogram and magnetoencephalogram can record neural signals with high temporal resolution at the millisecond level, which is uniquely suitable to interrogate cerebellar physiology. These techniques have recently been implemented to study cerebellar physiology in healthy subjects as well as individuals with movement disorders. In the present review, we focus on the current understanding of cerebellar physiology using these techniques to study movement disorders.

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Understorey light environment impacts on seedling establishment and growth in a typhoon-disturbed tropical forest - Kuo-Jung Chao; Yung-Chiau Lin; Guo-Zhang Michael Song; Chien-Hui Liao; Yau-Lun Kuo; Chang-Fu Hsieh; Eugene W. Schupp (Plant Ecology, 2022)

Altered glucose metabolism and its association with carbonic anhydrase 8 in Machado-Joseph Disease - Guan-Yu Lin; Chung-Yung Ma; Li-Chung Kuo; Benjamin Y. Hsieh; Hanbing Wang; Chin-San Liu; Mingli Hsieh (Metabolic Brain Disease, 2022)

Ocean acidification in the Western Pacific: Boron isotopic composition recorded in a tropical massive coral core from Lanyu Islet SE Taiwan - Chen-Feng You; P-Y. Lin; Kuo-Fang Huang; Chuan-Hsiung Chung; Zhifei Liu (Frontiers in Marine Science, 2022)
Boron (B) and B isotopic compositions (δ 11 B) in biogenic carbonates are useful proxies for pH reconstruction in the ocean. However, high-resolution archives are scarce due to associated sampling and analytical difficulty. In this study, a modern long-lived massive coral skeleton ( Porites lobata ) from Lanyu Islet off southeast Taiwan was drilled and used for high-resolution major/trace element analyses, including trace elements B and δ 11 B, as well as oxygen and carbon isotopes, to investigate the associated environmental changes during 1991–1997. To avoid complicated biological influence, the top-most tissue layer was excluded in this study. The coralline records show a clear temporal trend in metal/Ca-based sea surface temperatures (SSTs) on annual and monthly timescales. In particular, the Mg/Ca-SSTs, the most sensitive temperature proxy at the site, show a significant warming trend (+0.2°C year −1 ) during the study period. On the other hand, subtle changes in the annual δ 11 B record were identified, corresponding to ~0.2 pH unit, which is comparable with other coral records in the Pacific, e.g., the South China Sea (SCS), Guam Island, Flinders, and Arlington Reef, as well as the in-situ seawater pH measurement at Hawaii station. This corresponds to an acidification rate of ~0.25 pH unit 100 year −1 , similar to other coralline data, in-situ pH/pCO 2 measurement, or model predictions, and emphasizes the importance of ocean acidification due to anthropogenic activities. Combined with the Mg/Ca-SST, the intra-annual data show a clear seasonal cycle with higher pH in winter, consistent with the pCO 2 at the oceanic surface. These chemical and isotopic results in corals conclude that marine biogenic carbonates are informative for oceanic pH reconstruction and can provide new insights into the relationships between climate changes and environmental responses on the coast of Taiwan.

The Spatial Variation in Chlorophyte Community Composition From Coastal to Offshore Waters in a Subtropical Continental Shelf System - Yun-Chi Lin; Chien-Pang Chin; Wei-Ting Chen; Ching-Ting Huang; Gwo-Ching Gong; Kuo-Ping Chiang; Xin-Bei Chen (Frontiers in Marine Science, 2022)
Globally, the continental shelf occupies less than 10% of the total sea surface, but supports substantial primary production and fisheries. Photosynthetic picoeukaryotes (PPE) are important primary producers in marine ecosystems, and chlorophytes make a significant contribution to PPE abundance. Although the distribution of chlorophytes has been widely studied, little is known about how their community composition varies along the coastal-offshore gradient in subtropical continental shelf waters. To better understand their spatial variations, we employed metabarcoding data of 18S rRNA V4 gene to examine chlorophyte composition within the surface and deep chlorophyll maximum (DCM) layers over the continental shelf in the East China Sea (ECS) with high-resolution sampling. Our results indicate a higher chlorophyte diversity in the surface layer than in the DCM. In addition, we found that chlorophytes in oligotrophic Kuroshio surface water were the most diverse, with a higher percentage of Chloropicophyceae, prasinophyte clade V, prasinophyte clade IX, Palmophyllophyceae and Chlorodendrophyceae. In more eutrophic waters along the coast and within the DCM layer, chlorophytes were dominated by Mamiellophyceae. A significant spatial variation in community composition occurred along the nutrient gradient in the subtropical continental shelf ecosystem, varying from Mamiellophyceae-dominant in coastal water to Chloropicophyceae-dominant in offshore water. Furthermore, at a low saline coastal station, which had the lowest chlorophyte diversity, Picochlorum (Trebouxiophyceae) was dominant. Overall, chlorophyte diversity was positively correlated with temperature, and negatively correlated with silicate concentration. This study revealed that terrestrial input into continental systems influences chlorophyte diversity in the subtropical northwestern Pacific Ocean.

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Integrated small RNA profiling and degradome analysis of Anthurium andraeanum cultivars with different-colored spathes - Fazhuang Lin; Shi-Peng Chen; Kuan-Hung Lin; Changming Chen; Fengqin Yao; Linshan Zhong; Weiting Chen; Yun-Wei Kuo (Journal of Plant Research, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

Correction to: Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Growth Promotion and Salt-Tolerance Improvement of Gerbera jamesonii by Root Colonization of Piriformospora indica - Weiting Chen; Fazhuang Lin; Kuan-Hung Lin; Changming Chen; Chaoshui Xia; Qiaoling Liao; Shi-Peng Chen; Yun-Wei Kuo (Journal of Plant Growth Regulation, 2022)

Probiotics and their Metabolites Reduce Oxidative Stress in Middle-Aged Mice - Wen-Yang Lin; Jia-Hung Lin; Yi-Wei Kuo; Pei-Fang Rose Chiang; Hsieh-Hsun Ho (Current Microbiology, 2022)
Aging is an irreversible physiological degradation of living organisms. Accumulated oxidative stress and dysbiosis accelerate aging. Probiotics such as Lactobacillus and Bifidobacterium and their fermented metabolites (postbiotics) have been discovered to exhibit antioxidative activities that regulate oxidative stress and protect cells from oxidative damage. We screened selected Lactobacillus and Bifidobacterium strains and their postbiotics for potential antioxidative activity by using DPPH (2,2-Diphenyl-1-picrylhydrazyl) assay. Strains with their metabolites were selected for mixed formula in experiments involving aging mice. The aged groups presented higher oxidative stress in the brain, liver, heart, and kidney than did young mice. However, treatment with probiotic strains and their postbiotics elevated antioxidative levels, especially in the high-dose probiotics plus postbiotics group. Next-generation sequencing data revealed positive microbiota alterations of Lactobacillus and Bifidobacterium and Akkermansia in the gut. Lactobacillus johnsonii and Akkermansia muciniphila exhibited effective enlargement of relative abundance. Besides, high-dose probiotics and high-dose probiotics plus postbiotics showed significant elevation in serum SCFAs, especially in butyrate. In conclusion, the formula containing Bifidobacterium animalis subsp. infantis BLI-02, Bifidobacterium breve Bv889, Bifidobacterium bifidum VDD088, B. animalis subsp. lactis CP-9, and Lactobacillus plantarum PL-02 and their metabolites may benefit aged people’s health.

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Very Low Stocks and Inputs of Necromass in Wind-affected Tropical Forests - Kuo-Jung Chao; Pin-Siou Liao; Yi-Sheng Chen; Guo-Zhang Michael Song; Oliver L. Phillips; Hsing-Juh Lin (Ecosystems, 2022)

Structure related α-glucosidase inhibitory activity and molecular docking analyses of phenolic compounds from Paeonia suffruticosa - Po-Chun Chen; Bongani Sicelo Dlamini; Chiy-Rong Chen; Yueh-Hsiung Kuo; Wen-Ling Shih; Yun-Sheng Lin; Chien-Hsing Lee; Chi-I Chang (Medicinal Chemistry Research, 2022)

Study of the operative conditions and the optimum amount of municipal incinerator bottom ash for the obtainment of ceramic floor tiles - Deng-Fong Lin; Kuo-Liang Lin; Show-Ing Shieh; Chia-Wen Chen (Environmental Science and Pollution Research, 2022)

Multivariate analysis of the spatial species diversity of demersal fish assemblages in relation to habitat characteristics in a subtropical national park, Taiwan - Kuo-Shu Chen; Hsu-Sen Chen; Chiee-Young Chen; Yan-Lin Su; Pei-Jie Meng; Meng-Hsien Chen (Marine Biodiversity, 2022)
To understand the spatial species diversity of demersal fish assemblages in Taijiang National Park (TJNP) of Taiwan, fishes from 44 demersal trawl hauls and environmental data were collected in the nearshore and offshore areas of TJNP from April 2016 to May 2019. In total, fishes of 47 families, 84 genera, and 113 species were recorded. The nearshore and offshore demersal fish assemblages in TJNP exhibited significant variability in species composition assessed via beta diversity. Using distance-based redundancy analysis, we demonstrated that bottom depth and substrate type were significant explanatory variables of spatial species diversity and identified three habitat types (I: shallow soft bottom; II: deeper soft bottom; III: deeper bottom with mixed sand and gravel substrates). The nearshore assemblage was characterized by type I, where Tarphops oligolepis (flounder), Trachinocephalus myops (snakefish), and Liachirus melanospilos (carpet sole) dominated in terms of abundance. The offshore assemblage was characterized by either type II or type III because differences in substrate types among sampling sites were noticeable. At the offshore sites characterized by a deeper soft bottom (type II), Johnius distinctus (croaker), Cynoglossus kopsii (shortheaded tonguesole), and Coelorinchus formosanus (Formosa grenadier) predominated. In contrast, the westernmost sampling site, characterized by type III habitat, exhibited relatively high Shannon indices, and Scorpaena miostoma (scorpionfish), Urolophus aurantiacus (sepia stingray), and Parabothus taiwanensis (lefteye flounder) predominated. Our results provide the first baseline information on the environmental characteristics and spatial species diversity of demersal fish assemblages in TJNP and have implications for biodiversity conservation in existing spatial management areas.

Beryllium-7 and Lead-210 are Associated with an Increase in the Arctic Oscillation: Evidence from Atmospheric Aerosols in a Remote Tropical Region in East Asia - Xiaoxia Chen; Wuhui Lin; Xianwen He; Liangliang Feng; Kuo-Ying Wang (Asia-Pacific Journal of Atmospheric Sciences, 2022)
The Arctic Oscillation (AO) accounts for a large fraction of recent decadal climate trends in Northern Hemisphere (NH) high latitudes. In East Asia, an elevated AO index (AOI) was associated with warmer temperatures in middle- to high-latitude regions, colder temperatures over low-latitude regions, and elevated ozone intrusion from the stratosphere. Elevated beryllium-7 ( 7 Be) is produced in the stratosphere. Few studies have discussed the relationship between 7 Be and the AO. Here, we identify the AO signature in 7 Be and lead (Pb)-210 observed at a tropical ambient monitoring site in Nanning (22.8°N, 108.5°E) during the December 2014–December 2017 period. Our results show that the 7 Be and 210 Pb concentrations are positively and significantly correlated with the AOI ( P 7 Be and 210 Pb are associated with an increase in the AOI, reflecting air masses originating from NH high latitudes and vertically from the high-latitude upper troposphere and lower stratosphere regions to tropical latitudes in East Asia. These results have been verified with ozonesonde data without seasonality and with two meteorological data sets. Our results are also confirmed by observational data over the Pacific regions. We conclude that the AO exerts impacts over the tropical regions in East Asia, and 7 Be can be used as a tracer to track the impacts of the AO.

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

Electrical Impedance Tomography Analysis Between Two Similar Respiratory System Compliance During Decremetal PEEP Titration in ARDS Patients - Po-Lan Su; Wei-Chieh Lin; Yen-Fen Ko; Kuo-Sung Cheng; Chang-Wen Chen (Journal of Medical and Biological Engineering, 2021)
Purpose The positive end-expiratory pressure (PEEP) level with best respiratory system compliance (Crs) is frequently used for PEEP selection in acute respiratory distress syndrome (ARDS) patients. On occasion, two similar best Crs (where the difference between the Crs of two PEEP levels is < 1 ml/cm H 2 O) may be identified during decremental PEEP titration. Selecting PEEP under such conditions is challenging. The aim of this study was to provide supplementary rationale for PEEP selection by assessing the global and regional ventilation distributions between two PEEP levels in this situation. Methods Eight ARDS cases with similar best Crs at two different PEEP levels were analyzed using examination-specific electrical impedance tomography (EIT) measures and airway stress index (SIaw). Five Crs were measured at PEEP values of 25 cm H 2 O (PEEP 25 ), 20 cm H 2 O (PEEP 20 ), 15 cm H 2 O (PEEP H ), 11 cm H 2 O (PEEP I ), and 7 cm H 2 O (PEEP L ). The higher PEEP value of the two PEEPs with similar best Crs was designated as PEEP upper , while the lower designated as PEEP lower . Results PEEP H and PEEP I shared the best Crs in two cases, while similar Crs was found at PEEP I and PEEP L in the remaining six cases. SIaw was higher with PEEP upper as compared to PEEP lower (1.06 ± 0.10 versus 0.99 ± 0.09, p = 0.05). Proportion of lung hyperdistension was significantly higher with PEEP upper than PEEP lower (7.0 ± 5.1% versus 0.3 ± 0.5%, p = 0.0002). In contrast, proportion of recruitable lung collapse was higher with PEEP lower than PEEP upper (18.6 ± 4.4% versus 5.9 ± 3.7%, p < 0.0001). Cyclic alveolar collapse and reopening during tidal breathing was higher at PEEP lower than PEEP upper (34.4 ± 19.3% versus 16.0 ± 9.1%, p = 0.046). The intratidal gas distribution (ITV) index was also significantly higher at PEEP lower than PEEP upper (2.6 ± 1.3 versus 1.8 ± 0.7, p = 0.042). Conclusions PEEP upper is a rational selection in ARDS cases with two similar best Crs. EIT provides additional information for the selection of PEEP in such circumstances.

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Dynamic Changes in Soil Microbial Communities with Glucose Enrichment in Sediment Microbial Fuel Cells - Jimmy Kuo; Daniel Liu; Shuai-Hao Wang; Chorng-Horng Lin (Indian Journal of Microbiology, 2021)

Exercise renovates H2S and Nrf2-related antioxidant pathways to suppress apoptosis in the natural ageing process of male rat cortex - Jing-Ying Lin; Tsung-Jung Ho; Bruce Chi-Kang Tsai; Chien-Yi Chiang; Hui-Chuan Kao; Wei-Wen Kuo; Ray-Jade Chen; Vijaya Padma Viswanadha; Chi-Wen Huang; Chih-Yang Huang (Biogerontology, 2021)

miR-145-5p targets paxillin to attenuate angiotensin II-induced pathological cardiac hypertrophy via downregulation of Rac 1, pJNK, p-c-Jun, NFATc3, ANP and by Sirt-1 upregulation - Kuan-Ho Lin; V. Bharath Kumar; Tamilselvi Shanmugam; Marthandam Asokan Shibu; Ray-Jade Chen; Chia-Hua Kuo; Tsung-Jung Ho; V. Vijaya Padma; Yu-Lan Yeh; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

Combination of XGBoost Analysis and Rule-Based Method for Intrapartum Cardiotocograph Classification - Pao-Lin Kuo; Lim Bee Yen; Yi-Chun Du; Po-Fan Chen; Pei-Yin Tsai (Journal of Medical and Biological Engineering, 2021)

Characterization Of Secondary Metabolites From The Rhizome Of Cynara Scolymus And Their Antioxidant Properties - Chia-Lin Lee; Kuo-Chen Liao; Chien-Chih Chen; Yen-An Lin; Tung-Ying Wu; Yun-Lian Jhan; Chao-Jung Chen; Juan-Cheng Yang; Yang-Chang Wu (Natural Product Research, 2021)

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Effect of dermal phthalate levels on lung function tests in residential area near a petrochemical complex - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Hung Su; Jen-taie Shiea; Wen-Yi Lin; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

Cabbage defense response provoked by Trichoderma Th-LAAO - Chia-Min Liu; Shu-Ying Liu; Chuan-Kai Liao; Chaur-Tsuen Lo; Kuo-Chih Lin; Kou-Cheng Peng (Archives of Microbiology, 2021)

Effects of Climate Change in Marine Ecosystems Based on the Spatiotemporal Age Structure of Top Predators: A Case Study of Bigeye Tuna in the Pacific Ocean - Kuo-Wei Lan; Yan-Lun Wu; Lu-Chi Chen; Muhamad Naimullah; Tzu-Hsiang Lin (Frontiers in Marine Science, 2021)
How top predators behave and are distributed depend on the conditions in their marine ecosystem through bottom−up forcing; this is because where and when these predators can feed and spawn are limited and change often. This study investigated how the catch rates of immature and mature cohorts of bigeye tuna (BET) varied across space and time; this was achieved by analyzing data on the Taiwanese longline fishery in the western and central Pacific Ocean (WCPO). We also conducted a case study on the time series patterns of BET cohorts to explore the processes that underlie the bottom-up control of the pelagic ecosystem that are influenced by decadal climate events. Wavelet analysis results revealed crucial synchronous shifts in the connection between the pelagic ecosystems at low trophic levels in relation to the immature BET cohort. Many variables exhibited decreasing trends after 2004–2005, and we followed the Pacific Decadal Oscillation (PDO) as a bottom-up control regulator. The results indicated that low recruitment into the mature cohort occurs 3 years after a decrease in the immature cohort’s food stocks, as indicated by a 3-year lag in our results. This finding demonstrated that, by exploring the connection between low-trophic-level species and top predators at various life stages, we can better understand how climate change affects the distribution and abundance of predator fish.

Evidence-based Customized Ankle-Foot Orthosis with Energy Storage - Chih-Chun Lin; Chien-Hsien Yeh; Yi-Chun Tsai; Li-Chieh Kuo; Hsiu-Yun Hsu; Ping-Han Chuang; Kai Chang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

Decline of Seriatopora (Scleractinia: Pocilloporidae) fecundity in Taiwan in 2018–2019 - Luca Cirino; Sujune Tsai; Fu-Wen Kuo; Zhi-Hong Wen; Pei-Jie Meng; Chiahsin Lin (Marine Biology Research, 2021)

Improvement of Two-Dimensional Flow-Depth Prediction Based on Neural Network Models By Preprocessing Hydrological and Geomorphological Data - Pin-Chun Huang; Kuo-Lin Hsu; Kwan Tun Lee (Water Resources Management, 2021)

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Correction to: Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2021)

Piriformospora indica colonization increases the growth, development, and herbivory resistance of sweet potato (Ipomoea batatas L.) - Qing Li; Yun-Wei Kuo; Kuan-Hung Lin; Weiqun Huang; Caisheng Deng; Kai-Wun Yeh; Shi-Peng Chen (Plant Cell Reports, 2021)

Development and Usability Testing of a Decision Support App for Women Considering Breast Reconstruction Surgery - Pin-Jun Lin; Su-Ying Fang; Yao-Lung Kuo (Journal of Cancer Education, 2021)

Analysis of Meteorological Drought Resilience and Risk Assessment of Groundwater Using Signal Analysis Method - Yuan-Chien Lin; En-Dian Kuo; Wan-Ju Chi (Water Resources Management, 2021)

Deformation characteristics of unstable shallow slopes triggered by rainfall infiltration - Kuo-Hsin Yang; Thanh Son Nguyen; Harianto Rahardjo; Der-Guey Lin (Bulletin of Engineering Geology and the Environment, 2021)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

Feeding Habits of Bigeye Tuna (Thunnus obesus) in the Western Indian Ocean Reveal a Size-Related Shift in Its Fine-Scale Piscivorous Diet - Chien-Hsiang Lin; Jing-Siang Lin; Kuo-Shu Chen; Meng-Hsien Chen; Chiee-Young Chen; Chih-Wei Chang (Frontiers in Marine Science, 2020)

Hyperphosphorylation Renders Tau Prone to Aggregate and to Cause Cell Death - Mengyu Liu; Dexin Sui; Thomas Dexheimer; Stacy Hovde; Xiexiong Deng; Kuang-Wei Wang; Hsin Lian Lin; Hsiao-Tien Chien; Hye Kyong Kweon; Nora Sheen Kuo; Christopher A. Ayoub; Daniela Jimenez-Harrison; et al. (Molecular Neurobiology, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Technology-side carbon abatement cost curves for China’s power generation sector - Lin-Ju Chen; Zhen-Hai Fang; Fei Xie; Hai-Kuo Dong; Yu-Heng Zhou (Mitigation and Adaptation Strategies for Global Change, 2020)

Neglect of Presence of Bacteria Leads to Inaccurate Growth Parameters of the Oligotrich Ciliate Strombidium sp. During Grazing Experiments on Nanoflagellates - Wan-Lin Chen; Kuo-Ping Chiang; Sheng-Fang Tsai (Frontiers in Marine Science, 2020)

Future trends and guidance for the triple bottom line and sustainability: a data driven bibliometric analysis - Ming-Lang Tseng; Chia-Hao Chang; Chun-Wei Remen Lin; Kuo-Jui Wu; Qing Chen; Li Xia; Bing Xue (Environmental Science and Pollution Research, 2020)
This study conducts a comprehensive literature review of articles on the triple bottom line (TBL) published from January 1997 to September 2018 to provide significant insights and support to guide further discussion. There were three booms in TBL publications, occurring in 2003, 2011, and 2015, and many articles attempt to address the issue of sustainability by employing the TBL. This literature analysis includes 720, 132, and 58 articles from the Web of Science (WOS), Inspec, and Scopus databases, respectively, and reveals the gaps in existing research. To discover the barriers and points of overlap, these articles are categorized into six aspects of the TBL: economic, environmental, social, operations, technology, and engineering. Examining the top 3 journals in terms of published articles on each aspect reveals the research trends and gaps. The findings provide solid evidence confirming the argument that the TBL as currently defined is insufficient to cover the entire concept of sustainability. The social and engineering aspects still require more discussion to support the linkage of the TBL and to reinforce its theoretical basis. Additionally, to discover the gaps in the data sources, theories applied, methods adopted, and types of contributions, this article summarizes 82 highly cited articles covering each aspect. This article offers theoretical insights by identifying the top contributing countries, institutions, authors, keyword networks, and authorship networks to encourage scholars to push the current discussion further forward, and it provides practical insights to bridge the gap between theory and practice for enhancing the efficiency and effectiveness of improvements.

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Bias Adjustment of Satellite Precipitation Estimation Using Ground-Based Observation: Mei-Yu Front Case Studies in Taiwan - Nan-Ching Yeh; Yao-Chung Chuang; Hsin-Shuo Peng; Kuo-Lin Hsu (Asia-Pacific Journal of Atmospheric Sciences, 2020)
The Global Satellite Mapping of Precipitation (GSMaP) was used to estimate the accumulated rainfall in May from the Mei-Yu front in Taiwan. Rainfall estimation from GSMaP during 2002–2017 were evaluated using more than 400 local gauge observations, collected from the Taiwan Central Weather Bureau (CWB). Studies have demonstrated that the GSMaP rainfall estimation estimates can be biased, depending on the target region, elevation, and season. In this experiment, we have evaluated GSMaP over three elevation ranges. The GSMaP systemic errors for each elevation range were identified and corrected using regression analysis. The results indicated that GSMaP estimation can be improved significantly through adjustment over three elevation ranges (elevation less than 50 m, elevation of 50–100 m, and elevation higher than 100 m). For these three elevation ranges, the correlation coefficient between the GSMaP estimations and CWB rainfall data was 0.76, 0.78, and 0.59, respectively. This indicated that the GSMaP estimation was more accurate for low-elevation regions than high-elevation regions. After the proposed approaches were employed to correct the errors, the bias errors were respectively improved by 5.64(13.7%), 7.33(38.4%) and 10.52(31.2%) mm for low-, mid- and high-elevation regions. This study demonstrated that the local correction approaches can be used to improve GSMaP estimation of Mei-Yu rainfall in Taiwan.

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Population Genetic Analysis for Stock Enhancement of Silver Sea Bream (Rhabdosargus sarba) in Taiwan - Te-Hua Hsu; Chang-Wen Huang; Hung-Tai Lee; Yi-Hsuan Kuo; Kwang-Ming Liu; Cheng-Hui Lin; Hong-Yi Gong (Fishes, 2020)
Stock enhancement is a method for replenishing depleted wild finfish populations by supplementing them with hatchery-raised fish. In Taiwan, silver sea bream (Rhabdosargus sarba) is a predominant commercial species involved in stock enhancement projects. Although management agencies conduct stock enhancement projects, there are a lot of private releases without records. Stock enhancement is performed by the private aquaculture sector without accurate genetic records, potentially leading to unintended consequences for wild populations. We analyzed the genetics of 459 wild and 701 hatchery-reared specimens from nine batches produced by various hatcheries. Wild and hatchery-reared samples could be considered two separate clades by using a set of stable and informative microsatellite markers including type I (from gene introns and 3′UTR) and type II markers (randomly picked up from genome). Type I microsatellite markers could more sensitively reflect the loss of genetic diversity more than type II markers in the domestication process. All specimens were considered native by using mtDNA COI and microsatellites. The genetic composition of the wild population is relatively simple, and the estimated low contribution rate of the hatchery stock (1.3–10.9%; 6–50/459) indicated a weak but significant genetic effect of stock enhancement. Therefore, establishing standards for the stock enhancement of silver sea bream for more effective supplementation of wild populations is imperative.

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Large paleo-rockslide induced by buckling failure at Jiasian in Southern Taiwan - Che-Ming Yang; Keng-Hao Kang; Shun-Hsing Yang; Kuo-Wei Li; Hui-Jung Wang; Yin-Tsan Lee; Kuei-Kun Lin; Yii-Wen Pan; Jyh-Jong Liao (Landslides, 2020)

Calycosin Preserves BDNF/TrkB Signaling and Reduces Post-Stroke Neurological Injury after Cerebral Ischemia by Reducing Accumulation of Hypertrophic and TNF-α-Containing Microglia in Rats - Chien-Chin Hsu; Ting-Wei Kuo; Wen-Pin Liu; Ching-Ping Chang; Hung-Jung Lin (Journal of Neuroimmune Pharmacology, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Cerebellar Volume Is Associated with Cognitive Decline in Mild Cognitive Impairment: Results from ADNI - Chi-Ying Lin; Chi-Hua Chen; Sarah E. Tom; Sheng-Han Kuo (The Cerebellum, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Chemical fingerprint and source apportionment of PM2.5 in highly polluted events of southern Taiwan - Huazhen Shen; Tsung-mou Yang; Chun-chung Lu; Chung-shin Yuan; Chung-Hsuang Hung; Chi-tsan Lin; Chia-wei Lee; Guohua Jing; Gongren Hu; Kuo-cheng Lo (Environmental Science and Pollution Research, 2020)

The potential of satellite remote sensing for monitoring the onset of volcanic activity on Taipei’s doorstep - Hai-Po Chan; Chung-Pai Chang; Tang-Huang Lin; Matthew Blackett; Hao Kuo-Chen; Andrew Tien-Shun Lin (International Journal of Remote Sensing, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Presence of emerging contaminants in baby food - Maria Nobile; Francesco Arioli; Radmila Pavlovic; Federica Ceriani; Shih-Kuo Lin; Sara Panseri; Roberto Villa; Luca Maria Chiesa (Food Additives & Contaminants: Part A, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

LA-ICP-MS zircon U-Pb age and Hf isotope data from the granitic rocks in the Iwakuni area, Southwest Japan: re-evaluation of emplacement order and the source magma - Tayyaba Mateen; Kazuaki Okamoto; Sun-Lin Chung; Kuo-Lung Wang; Hao-Yang Lee; Shuhei Abe; Yuji Mita; Hafiz U. Rehman; Masaru Terabayashi; Hiroshi Yamamoto (Geosciences Journal, 2019)

The High-Frequency Decay Parameter (Kappa) in Taiwan - Shun-Chiang Chang; Kuo-Liang Wen; Ming-Wey Huang; Chun-Hsiang Kuo; Che-Min Lin; Chun-Te Chen; Jyun-Yan Huang (Pure and Applied Geophysics, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Spatial and temporal variations of sediment metals in the Tuul River, Mongolia - Tseren-Ochir Soyol-Erdene; Saulwood Lin; Enkhdul Tuuguu; Dorj Daichaa; Kuo-Ming Huang; Ulziibat Bilguun; Enkh-Amgalan Tseveendorj (Environmental Science and Pollution Research, 2019)

Cloning and overexpression of the ascorbate peroxidase gene from the yam (Dioscorea alata) enhances chilling and flood tolerance in transgenic Arabidopsis - Zhihua Chen; Hsueh-Han Lu; Shumei Hua; Kuan-Hung Lin; Ningdan Chen; Yangwen Zhang; Ziyi You; Yun-Wei Kuo; Shi-Peng Chen (Journal of Plant Research, 2019)

Different calcification responses of two hermatypic corals to CO2-driven ocean acidification - Xinqing Zheng; Fuwen Kuo; Ke Pan; Haining Huang; Rongcheng Lin (Environmental Science and Pollution Research, 2019)

Multi‐omic analyses of exogenous nutrient bag decomposition by the black morel Morchella importuna reveal sustained carbon acquisition and transferring - Hao Tan; Annegret Kohler; Renyun Miao; Tianhai Liu; Qiang Zhang; Bo Zhang; Lin Jiang; Yong Wang; Liyuan Xie; Jie Tang; Xiaolin Li; Lixu Liu; et al. (Environmental Microbiology, 2019)
Summary The black morel ( Morchella importuna Kuo, O'Donnell and Volk) was once an uncultivable wild mushroom, until the development of exogenous nutrient bag (ENB), making its agricultural production quite feasible and stable. To date, how the nutritional acquisition of the morel mycelium is fulfilled to trigger its fruiting remains unknown. To investigate the mechanisms involved in ENB decomposition, the genome of a cultivable morel strain ( M . importuna SCYDJ1‐A1) was sequenced and the genes coding for the decay apparatus were identified. Expression of the encoded carbohydrate‐active enzymes (CAZymes) was then analyzed by metatranscriptomics and metaproteomics in combination with biochemical assays. The results show that a diverse set of hydrolytic and redox CAZymes secreted by the morel mycelium is the main force driving the substrate decomposition. Plant polysaccharides such as starch and cellulose present in ENB substrate (wheat grains plus rice husks) were rapidly degraded, whereas triglycerides were accumulated initially and consumed later. ENB decomposition led to a rapid increase in the organic carbon content in the surface soil of the mushroom bed, which was thereafter consumed during morel fruiting. In contrast to the high carbon consumption, no significant acquisition of nitrogen was observed. Our findings contribute to an increasingly detailed portrait of molecular features triggering morel fruiting.

Extracting region-specific runout behavior and rainfall thresholds for massive landslides using seismic records: a case study in southern Taiwan - Ching Hung; Guan-Wei Lin; Ben Leshchinsky; Hsien-Li Kuo (Bulletin of Engineering Geology and the Environment, 2019)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

Phytochemical composition and larvicidal activity of essential oils from herbal plants - Hsiang-Ting Huang; Chien-Chung Lin; Tai-Chih Kuo; Shiang-Jiuun Chen; Rong-Nan Huang (Planta, 2019)

Using a numerical method to precisely evaluate the alpha angle in a hip image - Chung-Liang Lai; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Hsiao-Che Lin; Chin-Liang Kuo; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2019)

Assessment of seven CMIP5 model precipitation extremes over Iran based on a satellite‐based climate data set - Pari‐Sima Katiraie‐Boroujerdy; Ata Akbari Asanjan; Ali Chavoshian; Kuo‐lin Hsu; Soroosh Sorooshian (International Journal of Climatology, 2019)
The ability of the seven CMIP5 models to simulate extreme precipitation events over Iran was evaluated using the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks–Climate Data Record (PERSIANN‐CDR) data set. The criterion used to select the CMIP5 models was the availability of historical daily precipitation data (PERSIANN‐CDR) for the retrospective period 1983–2005, as well as future projections for the three representative concentration pathways emission scenarios (RCP2.6, RCP4.5, and RCP8.5) and spatial resolution higher than 2 × 2°. This is the first study to focus on extreme precipitation climate model simulations over Iran that includes high topography and different climates. The results show that CCSM4 has the highest correlation coefficients (CC = 0.85) and lowest root‐mean‐square error (RMSE = 73.6 mm) compared to PERSIANN‐CDR for the mean annual precipitation. However, HadGEM2‐ES shows the best (highest CCs between 0.67–0.79 and almost the lowest root‐mean‐square errors [RMSEs] compared to PERSIANN‐CDR) performance for intensity indices; MIROC5 ranked seventh (least CCs and almost the highest RMSEs) among the selected models. The results show that BCC‐CSM1‐1‐M captures maximum consecutive dry days (CDD) better than the other models. The probability matching method (PMM) is used to bias‐correct daily precipitation events from CMIP5 models with respect to the PERSIANN‐CDR estimations. All the model performances designed to capture the mean annual precipitation, as well as extreme intensity indices, improved after correction. The ensemble, constructed from the bias‐corrected model simulations using multiple linear regression (MLR), has the best performance for simulating the mean annual precipitation and extreme indices (CCs between 0.82 for consecutive wet days [CWD] and 0.93 for the mean annual precipitation) compared to the PERSIANN‐CDR estimations. Among the seven selected models, CCSM4 has the highest ranking (CCs between 0.70 for CWD to 0.91 for mean annual precipitation) after bias correction.

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

SSPHE special session on environmental science, pollution, and sustainability - Kuo-Lin Huang; Xi Peng (Environmental Science and Pollution Research, 2019)

Cover Image - Theeraporn Pulpipat; Kuo‐Hua Lin; Ying‐Hao Chen; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2019)

Molecular characterization and pathogenicity of Francisella noatunensis subsp. orientalis isolated from cultured tilapia ( Oreochromis sp.) in Taiwan - Theeraporn Pulpipat; Kuo‐Hua Lin; Ying‐Hao Chen; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2019)
Francisella noatunensis subsp. orientalis is a causative agent of systemic granulomatous disease in tilapia. The present study was designed to understand the genetic and phenotypic diversities among Taiwanese Fno isolates obtained from tilapia ( n = 17) and green Texas cichlid ( Herichthys cyanoguttatus ) ( n = 1). The enzymatic profiles of the isolates were studied using the API ZYM system. Phylogenetic tree analysis of the 16S rRNA and housekeeping gene and pulsed‐field gel electrophoresis (PFGE) were carried out to determine the genotypic characters of all isolates. The phylogenetic tree showed similarity of 99%–100% nucleotide sequences of 16S rRNA and housekeeping genes compared to the Fno references genes from GenBank database. Comparatively, the results revealed an identical profile of enzymatic and PFGE pattern which was distincted from that of F. philomiragia . To understand the pathogenicity, the isolates were intraperitoneal injected to tilapia the gross lesions were observed concomitant with natural outbreak. Median lethal dose upon Nile tilapia and red tilapia were 9.06 × 10 3 CFU/fish and 2.08 × 10 2 CFU/fish, respectively. Thus, our data provide understanding the epidemiology of Taiwanese Fno isolates, and help in development of future control and prevention.

Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

The effect of paclobutrazol on soil bacterial composition across three consecutive flowering stages of mung bean - Jimmy Kuo; Yen-Wen Wang; Michael Chen; Georgia Fuh; Chorng-Horng Lin (Folia Microbiologica, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Benefit analysis of flood adaptation under climate change scenario - Hsin-Chi Li; Shih-Yun Kuo; Wei-Bo Chen; Lee-yaw Lin (Natural Hazards, 2019)

Effects of a Web-based Health Education Program on Quality of Life and Symptom Distress of Initially Diagnosed Advanced Non-Small Cell Lung Cancer Patients: A Randomized Controlled Trial - Chi-Chin Huang; Han-Pin Kuo; Yueh-E Lin; Shu-Ching Chen (Journal of Cancer Education, 2019)

Levels and distribution of PBDEs and PFASs in pork from different European countries - Luca Maria Chiesa; Shih-Kuo Lin; Federica Ceriani; Sara Panseri; Francesco Arioli (Food Additives & Contaminants: Part A, 2018)

Plasminogen/thrombomodulin signaling enhances VEGF expression to promote cutaneous wound healing - Tsung-Lin Cheng; Po-Ku Chen; Wei-Kai Huang; Cheng-Hsiang Kuo; Chia-Fong Cho; Kuan-Chieh Wang; Guey-Yueh Shi; Hua-Lin Wu; Chao-Han Lai (Journal of Molecular Medicine, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Soil gas survey in and around Shanchiao fault of northern Taiwan for establishing continuous monitoring station - Arvind Kumar; Vivek Walia; Yi-Chun Sung; Shih-Jung Lin; Ching-Chou Fu; Kuo-Liang Wen (Acta Geophysica, 2018)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Modeling of the strong ground motion of 25th April 2015 Nepal earthquake using modified semi-empirical technique - Sohan Lal; A. Joshi; Sandeep; Monu Tomer; Parveen Kumar; Chun-Hsiang Kuo; Che-Min Lin; Kuo-Liang Wen; M. L. Sharma (Acta Geophysica, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Residue characteristics of sludge from a chemical industrial plant by microwave heating pyrolysis - Kuo-Hsiung Lin; Nina Lai; Jun-Yan Zeng; Hung-Lung Chiang (Environmental Science and Pollution Research, 2018)

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Using marker gene analysis instead of mixed lymphocyte reaction assay for identification of functional CD4+FOXP3+ regulatory T cells - Sin-Tak Chu; Kuo-Hsuan Chien; Hsiu-Hsia Lin; Wei-Hao Wu; Jhih-Yun Jian; Woan-Fang Tzeng; Tzeon-Jye Chiou (Biotechnology Letters, 2018)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Evaluation of a new satellite‐based precipitation data set for climate studies in the Xiang River basin, southern China - Qian Zhu; Kuo‐lin Hsu; Yue‐Ping Xu; Tiantian Yang (International Journal of Climatology, 2017)
A new satellite‐based precipitation data set, Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks‐Climate Data Record ( PERSIANN‐CDR ), with long‐term time series dating back to 1983, can be one valuable data set for climate studies. This study investigates the feasibility of using PERSIANN‐CDR as a reference data set for climate studies. Sixteen Coupled Model Intercomparison Projection Phase 5 ( CMIP5 ) models are evaluated over the Xiang River basin, southern China, by comparing their performance on precipitation projection and streamflow simulation, particularly on extreme precipitation and streamflow events. The results show PERSIANN‐CDR is a valuable data set for climate studies, even on extreme precipitation events. The precipitation estimates and their extreme events from CMIP5 models are improved significantly compared with rain gauge observations after bias correction by the PERSIANN‐CDR precipitation estimates. Given streamflows simulated with raw and bias‐corrected precipitation estimates from 16 CMIP5 models, 10 out of 16 are improved after bias correction. The impact of bias correction on extreme events for streamflow simulations are unstable, with 8 out of 16 models can be clearly claimed they are improved after the bias correction. Concerning the performance of raw CMIP5 models on precipitation, IPSL‐CM5A‐MR excels the other CMIP5 models, while MRI‐CGCM3 outperforms on extreme events with its better performance on six extreme precipitation metrics. Case studies also show that raw CCSM4 , CESM1‐CAM5 , and MRI‐CGCM3 outperform other models on streamflow simulation, while MIROC5‐ESM‐CHEM , MIROC5‐ESM , and IPSL‐CM5A‐MR behave better than the other models after bias correction.

Trends of precipitation extreme indices over a subtropical semi-arid area using PERSIANN-CDR - Pari-Sima Katiraie-Boroujerdy; Hamed Ashouri; Kuo-lin Hsu; Soroosh Sorooshian (Theoretical and Applied Climatology, 2017)

17β-Estradiol and/or estrogen receptor alpha blocks isoproterenol-induced calcium accumulation and hypertrophy via GSK3β/PP2A/NFAT3/ANP pathway - Peiying Pai; Bharath Kumar Velmurugan; Chia-Hua Kuo; Chung-Yi Yen; Tsung-Jung Ho; Yueh-Min Lin; Yu-Feng Chen; Chao-Hung Lai; Cecilia Hsuan Day; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2017)

Influence of Thread Design on Dental Implant Osseointegration Assayed Using the Lan-Yu Mini-Pig Model - Shih-Kang Chien; Shui-Sang Hsue; Chih-Shing Lin; Tzong-Fu Kuo; Duen-Jeng Wang; Jen-Chang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Complete nucleotide sequences of M and L RNAs from a new pepper-infecting tospovirus, Pepper chlorotic spot virus - Kuo-Shiou Huang; Chia-Hsing Tai; Ying-Huey Cheng; Shu-Hui Lin; Tsung-Chi Chen; Fuh-Jyh Jan (Archives of Virology, 2017)

HCV core inhibits hepatocellular carcinoma cell replicative senescence through downregulating microRNA-138 expression - Tzu-Yue Shiu; Yu-Lueng Shih; An-Chieh Feng; Hsuan-Hwai Lin; Shih-Ming Huang; Tien-Yu Huang; Chung-Bao Hsieh; Wei-Kuo Chang; Tsai-Yuan Hsieh (Journal of Molecular Medicine, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Development of a TaqMan probe-based insulated isothermal PCR (TiiPCR) for the detection of Acidovorax citrulli, the bacterial pathogen of watermelon fruit blotch - Pei-Yi Wu; Lien-Chun Ho; Jun-Jie Chang; Kuo-Ching Tzeng; Wen-Ling Deng; Yi-Hsien Lin (European Journal of Plant Pathology, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Detection of chlorophylls in spores of seven ferns - Mei-Hwei Tseng; Kuei-Huei Lin; Yi-Jia Huang; Ya-Lan Chang; Sheng-Cih Huang; Li-Yaung Kuo; Yao-Moan Huang (Journal of Plant Research, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

A mechanism of low molecular weight fucoidans degraded by enzymatic and acidic hydrolysis for the prevention of UVB damage - Pai-An Hwang; Ming-De Yan; Ko-Liang Kuo; Nam Nhut Phan; Yen-Chang Lin (Journal of Applied Phycology, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

The modulation of Th2 immune pathway in the immunosuppressive effect of human umbilical cord mesenchymal stem cells in a murine asthmatic model - Chin-Kan Chan; Ting-Chun Lin; Yung-An Huang; Ya-Shan Chen; Chia-Ling Wu; Huei-Yu Lo; Ming-Ling Kuo; Kang-Hsi Wu; Jing-Long Huang (Inflammation Research, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Design of wireless multi-parameter monitoring system for oral feeding of premature infants - Yu-Lin Wang; Hsing-Chien Kuo; Lin-Yu Wang; Mei-Ju Ko; Bor-Shyh Lin (Medical & Biological Engineering & Computing, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Regeneration of cerium(IV) in different spent chromium-etching solutions collected from thin-film transistor liquid crystal display manufacturing factories - Kuo-Lin Huang; Te-San Chen; Ren-Wei Tsai; Yu-Syuan Chen (Clean Technologies and Environmental Policy, 2016)

Mono(2-ethylhexyl)phthalate accumulation disturbs energy metabolism of fat cells - Huai-chih Chiang; Ya-Ting Kuo; Chih-Che Shen; Yi-Hua Lin; Shu-Li Wang; Tsui-Chun Tsou (Archives of Toxicology, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Quantifying the reliability of four global datasets for drought monitoring over a semiarid region - Pari-Sima Katiraie-Boroujerdy; Nasrin Nasrollahi; Kuo-lin Hsu; Soroosh Sorooshian (Theoretical and Applied Climatology, 2016)

Groundwater Molybdenum from Emerging Industries in Taiwan - Kuo-Sheng Tsai; Yu-Min Chang; Jimmy C. M. Kao; Kae-Long Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Aryl hydrocarbon receptor agonists upregulate VEGF secretion from bronchial epithelial cells - Ming-Ju Tsai; Tsu-Nai Wang; Yi-Shiuan Lin; Po-Lin Kuo; Ya-Ling Hsu; Ming-Shyan Huang (Journal of Molecular Medicine, 2015)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

2,3,5-Trimethoxy-4-cresol, an anti-metastatic constituent from the solid-state cultured mycelium of Antrodia cinnamomea and its mechanism - Chin-Chung Lin; Ching-Chun Chen; Yueh-Hsiung Kuo; Jong-Tar Kuo; K. J. Senthil Kumar; Sheng-Yang Wang (Journal of Natural Medicines, 2015)

Simulation of the records of the 27 March 2013 Nantou Taiwan earthquake using modified semi-empirical approach - A. Joshi; Chun-Hsiang Kuo; Piu Dhibar; Sandeep; M. L. Sharma; Kuo-Liang Wen; Che-Min Lin (Natural Hazards, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Pretreatment with Evans blue, a stimulator of BKCa channels, inhibits compound 48/80-induced shock, systemic inflammation, and mast cell degranulation in the rat - Yaw-Syan Fu; Su-Yu Kuo; Hsuan-Yea Lin; Chun-Lin Chen; Shi-Ying Huang; Zhi-Hong Wen; Kun-Zer Lee; Hung-Tu Huang (Histochemistry and Cell Biology, 2015)

Multi-muscle coordination during a challenging stance - Wen-Chieh Yang; Chih-Hsiu Cheng; Hsing-Kuo Wang; Kwan-Hwa Lin; Wei-Li Hsu (European Journal of Applied Physiology, 2015)

Photodegradation of Alachlor Using BiVO4 Photocatalyst Under Visible Light Irradiation - Yi-Kuo Chang; Yu-Shen Wu; Chung-Shin Lu; Pei-Feng Lin; Tsung-Yen Wu (Water, Air, & Soil Pollution, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Characterization of four B-chromosome-specific RAPDs and the development of SCAR markers on the maize B-chromosome - Kuo-Wei Kao; Chien-Yu Lin; Shu-Fen Peng; Ya-Ming Cheng (Molecular Genetics and Genomics, 2015)

Classification of Benign and Malignant Breast Tumors in Ultrasound Images with Posterior Acoustic Shadowing Using Half-Contour Features - Zhuhuang Zhou; Shuicai Wu; King-Jen Chang; Wei-Ren Chen; Yung-Sheng Chen; Wen-Hung Kuo; Chung-Chih Lin; Po-Hsiang Tsui (Journal of Medical and Biological Engineering, 2015)

Exploring the benefits of growing bioenergy crops to activate lead-contaminated agricultural land: a case study on sweet potatoes - Shu-Fen Cheng; Chin-Yuan Huang; Kuo-Lin Chen; Sheng-Chien Lin; Yung-Cheng Lin (Environmental Monitoring and Assessment, 2015)

Integrated assessment of China’s agricultural vulnerability to climate change: a multi-indicator approach - Yingchun Li; Wei Xiong; Wei Hu; Pam Berry; Hui Ju; Erda Lin; Wen Wang; Kuo Li; Jie Pan (Climatic Change, 2015)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Expansion of regulatory T cells from umbilical cord blood and adult peripheral blood CD4+CD25+ T cells - Syh-Jae Lin; Chun-Hao Lu; Dah-Chin Yan; Pei-Tzu Lee; Hsiu-Shan Hsiao; Ming-Ling Kuo (Immunologic Research, 2014)

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea - Yi Chang; Jui-Wen Chan; Yuan-Chao Angelo Huang; Wei-Quan Lin; Ming-An Lee; Kuo-Tien Lee; Cheng-Hsin Liao; Kae-Yih Wang; Yi-Chun Kuo (International Journal of Remote Sensing, 2014)

Improvement of earthquake locations with the Marine Cable Hosted Observatory (MACHO) offshore NE Taiwan - Nai-Chi Hsiao; Tzu-Wei Lin; Shu-Kun Hsu; Kai-Wei Kuo; Tzay-Chyn Shin; Peih-Lin Leu (Marine Geophysical Research, 2014)

Modified high-intensity interval training increases peak cardiac power output in patients with heart failure - Shu-Chun Huang; Mei-Kuen Wong; Pyng-Jing Lin; Feng-Chun Tsai; Tieh-cheng Fu; Ming-Shien Wen; Chi-Tai Kuo; Jong-Shyan Wang (European Journal of Applied Physiology, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Vine cuttings as possible initial inoculum sources of Ralstonia solanacearum race 1 biovar 4 on vegetable sweet potato in fields - Yi-Jeng Chen; Yi-Sheng Lin; Kuo-Jin Tseng; Wen-Hsin Chung (European Journal of Plant Pathology, 2014)

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Mitochondrial DNA phylogeography of Semisulcospira libertina (Gastropoda: Cerithioidea: Pleuroceridae): implications the history of landform changes in Taiwan - Kui-Ching Hsu; Hor Bor; Hung-Du Lin; Po-Hsun Kuo; Mian-Shin Tan; Yuh-Wen Chiu (Molecular Biology Reports, 2014)

Aryl hydrocarbon receptor (AhR) agonists increase airway epithelial matrix metalloproteinase activity - Ming-Ju Tsai; Ya-Lin Hsu; Tsu-Nai Wang; Ling-Yu Wu; Chi-Tun Lien; Chih-Hsing Hung; Po-Lin Kuo; Ming-Shyan Huang (Journal of Molecular Medicine, 2014)

GIS and SBF for estimating groundwater recharge of a mountainous basin in the Wu River watershed, Taiwan - HSIN-FU YEH; HUNG-I LIN; SHING-TSZ LEE; MIN-HSIANG CHANG; KUO-CHIN HSU; CHENG-HAW LEE (Journal of Earth System Science, 2014)

Cloning and gene expression analysis of sponge gourd ascorbate peroxidase gene and winter squash superoxide dismutase gene under respective flooding and chilling stresses - Chih Ming Chiang; Wen Shuo Kuo; Kuan Hung Lin (Horticulture, Environment, and Biotechnology, 2014)

Using ADABOOST and Rough Set Theory for Predicting Debris Flow Disaster - Ping-Feng Pai; Lan-Lin Li; Wei-Zhan Hung; Kuo-Ping Lin (Water Resources Management, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Gemifloxacin inhibits migration and invasion and induces mesenchymal–epithelial transition in human breast adenocarcinoma cells - Tun-Chieh Chen; Ya-Ling Hsu; Yu-Chieh Tsai; Yu-Wei Chang; Po-Lin Kuo; Yen-Hsu Chen (Journal of Molecular Medicine, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Anti-neuroinflammatory Effect of a Novel Caffeamide Derivative, KS370G, in Microglial cells - Dah-Yuu Lu; Bor-Ren Huang; Wei-Lan Yeh; Hsiao-Yun Lin; Shiang-Suo Huang; Yu-Shu Liu; Yueh-Hsiung Kuo (Molecular Neurobiology, 2013)

Aerosol characteristics of different types of episode - Chung-Yih Kuo; Yan-Ruei Lin; Shih-Yu Chang; Chuan-Yao Lin; Chun-Hung Chou (Environmental Monitoring and Assessment, 2013)

Altered molecular repertoire of immune system by renal dysfunction in the elderly: is prediction and targeted prevention in the horizon? - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Chih-Kang Chiang; Kuo-Cheng Lu (EPMA Journal, 2013)
Background Patients on chronic hemodialysis (HD) have impaired cellular and humoral immunity. The percentage of elderly people among the total population in Taiwan is increasing dramatically, and HD is the primary alternative for renal replacement therapy when renal function declines. Activated vitamin D is widely used in HD patients with secondary hyperparathyroidism (SHPT) and is a well-known immunomodulatory agent. Personalized medicine and integrative medical approach has been a trend in current clinical practice. Can we improve their immune function using vitamin D in spite of the mineral aspect? Here, we investigated the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and T cell differentiation in chronic HD patients. Methods Forty patients with chronic HD were enrolled. HD patients with SHPT had been treated with activated vitamin D for 3 months. Peripheral blood mononuclear cells obtained from the patients were cultured and stimulated by mitogens, and T cells were analyzed by flow cytometry. Serum 25(OH)D levels were detected by enzyme-linked immunosorbent assay. Results The incidence of T cell differentiation to the T helper cell (Th)2 subtype was more prevalent in the elderly group than in the controls ( p = 0.001). Th2 differentiation was also correlated with age ( p = 0.004) and serum 25(OH)D levels ( p < 0.05). After treated with activated vitamin D, the level of Th1 cytokines decreased while the Th2 cytokine level increased in the sera ( p < 0.05). The T cell differentiation tended toward the Th2 subtype ( p = 0.027) after treatment of activated vitamin D in SHPT patients. Conclusions These results demonstrated that Th2 differentiation is correlated with age and the serum 25(OH)D level of patients. Treatment with activated vitamin D influenced T cell differentiation and cytokine expression in SHPT patients. Taking vitamin D is the possible prediction and targeted treatment in the immune dysfunction in chronic HD patients.

Chemical constituents comparison of Codonopsis tangshen Codonopsis pilosula var. modesta and Codonopsis pilosula - Lie-Chwen Lin; Tung-Hu Tsai; Chao-Lin Kuo (Natural Product Research, 2013)

Augmenting satellite precipitation estimation with lightning information - Majid Mahrooghy; Valentine G. Anantharaj; Nicolas H. Younan; Walter A. Petersen; Kuo-Lin Hsu; Ali Behrangi; James Aanstoos (International Journal of Remote Sensing, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Emission factor of exhaust gas constituents during the pyrolysis of zinc chloride immersed biosolid - Hung-Lung Chiang; Kuo-Hsiung Lin; Hua-Hsien Chiu (Environmental Science and Pollution Research, 2013)

Effect of acute DHEA administration on free testosterone in middle-aged and young men following high-intensity interval training - Te-Chih Liu; Che-Hung Lin; Chih-Yang Huang; John L. Ivy; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

Estimation of phosphorus flux in rivers during flooding - Yen-Chang Chen; Jih-Hung Liu; Jan-Tai Kuo; Cheng-Fang Lin (Environmental Monitoring and Assessment, 2013)

Differential distribution and activation of microglia in the brain of male C57BL/6J mice - Ting-Ting Yang; Chingju Lin; Chao-Tien Hsu; Tzu-Feng Wang; Fang-Yi Ke; Yu-Min Kuo (Brain Structure and Function, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

Using the orthogonal projections methods for predicting rice ( Oryza sativa L.) yield with canopy reflectance data - Wen-Shin Lin; Bo-Jein Kuo (International Journal of Remote Sensing, 2013)

Comparative and reliability studies of neuromechanical leg muscle performances of volleyball athletes in different divisions - Chi-Pang Un; Kwan-Hwa Lin; Tzyy-Yuang Shiang; En-Chung Chang; Sheng-Chu Su; Hsing-Kuo Wang (European Journal of Applied Physiology, 2013)

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion - Pei-Chun Liao; Louis Kuoping Chao; Ju-Ching Chou; Wei-Chih Dong; Chien-Nan Lin; Chai-Yi Lin; Ann Chen; Shuk-Man Ka; Chen-Lung Ho; Kuo-Feng Hua (Inflammation Research, 2013)

Effect evaluation of shotcrete vegetation mulching technique applied to steep concrete-face slopes on a highway of Taiwan - Jen-Chen Fan; Chien-Lin Huang; Chih-Hsiang Yang; Kuo-Wei Liao; Wen-Wen Liao (Paddy and Water Environment, 2013)

An Electrochemical Approach to Simultaneous Determination of Acetaminophen and Ofloxacin - Te-San Chen; Kuo-Lin Huang; Jia-Long Chen (Bulletin of Environmental Contamination and Toxicology, 2012)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Effect of Sulfate Availability on the Isotopic Signature of Reduced Sulfurous Compounds in the Sediments of a Subtropical Estuary - Lan-Feng Fan; Saulwood Lin; Wei-Gang He; Kuo-Ming Huang; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2012)

High glucose increases nitric oxide generation in lipopolysaccharide-activated macrophages by enhancing activity of protein kinase C-α/δ and NF-κB - Kuo-Feng Hua; Szu-Hsuan Wang; Wei-Chih Dong; Chai-Yi Lin; Chen-Lung Ho; Tzu-Hua Wu (Inflammation Research, 2012)

Synergistic effects of streptolysin S and streptococcal pyrogenic exotoxin B on the mouse model of group A streptococcal infection - Chih-Hsin Hung; Nina Tsao; Yi-Fang Zeng; Shiou-Ling Lu; Chuan Chiang-Ni; Yee-Shin Lin; Jiunn-Jong Wu; Chih-Feng Kuo (Medical Microbiology and Immunology, 2012)

The effect of the red wine polyphenol resveratrol on a rat model of biliary obstructed cholestasis: involvement of anti-apoptotic signalling, mitochondrial biogenesis and the induction of autophagy - Tsu-Kung Lin; Li-Tung Huang; Ying-Hsien Huang; Mao-Meng Tiao; Kuo-Shu Tang; Chia-Wei Liou (Apoptosis, 2012)

A new phenylalkanoid from the rhizomes of Zingiber officinale - Soong-Yu Kuo; Rong-Jyh Lin; Yu-Ting Yeh; Jun-Yen Lee; Chung-Yi Chen (Natural Product Research, 2012)

Elevated risk of hypertension induced by arsenic exposure in Taiwanese rural residents: possible effects of manganese superoxide dismutase (MnSOD) and 8-oxoguanine DNA glycosylase (OGG1) genes - Shiuan-Chih Chen; Chun-Chieh Chen; Chung-Yih Kuo; Chun-Huang Huang; Chin-Hsiu Lin; Zi-Yun Lu; Yi-Yu Chen; Hong-Shen Lee; Ruey-Hong Wong (Archives of Toxicology, 2012)

Liquefaction potential and post-liquefaction settlement evaluations of the Chuoshui River Alluvial Fan in Taiwan - Muhsiung Chang; Chih-ping Kuo; Ron-eeh Hsu; Shih-hui Shau; Tin-mei Lin (Bulletin of Engineering Geology and the Environment, 2012)

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Bp5250 inhibits vascular endothelial growth factor-induced angiogenesis and HIF-1α expression on endothelial cells - Kuan-Ting Lin; Jin-Cherng Lien; Ching-Hu Chung; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Suburban atmospheric visibility sensing by an image degradation processor: model development and field test - Chin-Hsiang Luo; Kuo-Hung Lin; Che-Yen Wen; Shih-Hsuan Chiu; Chung-Shin Yuan; Shinhao Yang (International Journal of Remote Sensing, 2011)

Seasonal changes in atrophy-associated proteins of the sonic muscle in the big-snout croaker, Johnius macrorhynus (Pisces, Sciaenidae), identified by using a proteomic approach - Yuan-Chih Lin; Kuo-Hsun Chiu; Jentaie Shiea; Hurng-Wern Huang; Hin-Kiu Mok (Fish Physiology and Biochemistry, 2011)

Variability of sea surface temperature and warm pool area in the South China Sea and its relationship to the western Pacific warm pool - Chun-Yi Lin; Chung-Ru Ho; Quanan Zheng; Shih-Jen Huang; Nan-Jung Kuo (Journal of Oceanography, 2011)

Correlating recurrent radon precursors with local earthquake magnitude and crust strain near the Chihshang fault of eastern Taiwan - T. Kuo; C. Lin; C. Su; C. Liu; C. H. Lin; C. Chang; C. Chiang (Natural Hazards, 2011)

Satellite altimeter observations of nonlinear Rossby eddy–Kuroshio interaction at the Luzon Strait - Quanan Zheng; Chang-Kuo Tai; Jianyu Hu; Hongyang Lin; Rong-Hua Zhang; Feng-Chun Su; Xiaofeng Yang (Journal of Oceanography, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

A comparative study on arsenic and humic substances in alluvial aquifers of Bengal delta plain (NW Bangladesh), Chianan plain (SW Taiwan) and Lanyang plain (NE Taiwan): implication of arsenic mobilization mechanisms - A. H. M. Selim Reza; Jiin-Shuh Jean; Huai-Jen Yang; Ming-Kuo Lee; Hua-Fen Hsu; Chia-Chuan Liu; Yao-Chang Lee; Jochen Bundschuh; Kao-Hong Lin; Chi-Yu Lee (Environmental Geochemistry and Health, 2011)

Bioavailability Study of Berberine and the Enhancing Effects of TPGS on Intestinal Absorption in Rats - Wei Chen; Yu-Qiang Miao; Dong-Jiao Fan; Shen-Shen Yang; Xia Lin; Ling-Kuo Meng; Xing Tang (AAPS PharmSciTech, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Production of reactive oxygen species and induction of signaling pathways for the ACO gene expressions in tomato plants triggered by the volatile organic compound ether - Kuo-Chih Lin; Pi-Chi Sun; Pei-Lan Lin (Plant Cell Reports, 2011)

Risk assessment of inhalation exposure to polycyclic aromatic hydrocarbons in Taiwanese workers at night markets - Ping Zhao; Kuo-Pin Yu; Chi-Chi Lin (International Archives of Occupational and Environmental Health, 2011)

Population structure of Nouelia insignis (Asteraceae), an endangered species in southwestern China, based on chloroplast DNA sequences: recent demographic shrinking - Xun Gong; Shan-Shan Luan; Kuo-Hsiang Hung; Chi-Chuan Hwang; Chung-Jean Lin; Yu-Chung Chiang; Tzen-Yuh Chiang (Journal of Plant Research, 2011)

Celecoxib induces heme oxygenase-1 expression in macrophages and vascular smooth muscle cells via ROS-dependent signaling pathway - Jang-Shiun Wang; Feng-Ming Ho; Hao-Cheng Kang; Wan-Wan Lin; Kuo-Chin Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Typhoon Disturbance and Forest Dynamics: Lessons from a Northwest Pacific Subtropical Forest - Teng-Chiu Lin; Steven P. Hamburg; Kuo-Chuan Lin; Lih-Jih Wang; Chung-Te Chang; Yue-Joe Hsia; Matthew A. Vadeboncoeur; Cathy M. Mabry McMullen; Chiung-Pin Liu (Ecosystems, 2011)

The impact of microphysical schemes on hurricane intensity and track - Wei-Kuo Tao; Jainn Jong Shi; Shuyi S. Chen; Stephen Lang; Pay-Liam Lin; Song-You Hong; Christa Peters-Lidard; Arthur Hou (Asia-Pacific Journal of Atmospheric Sciences, 2011)

BNIP3 induces IL6 and calcineurin/NFAT3 hypertrophic-related pathways in H9c2 cardiomyoblast cells - Yi-Jiun Weng; Wei-Wen Kuo; Chia-Hua Kuo; Kwong-Chung Tung; Chang-Hai Tsai; James A. Lin; Fuu-Jen Tsai; Dennis Jine-Yuan Hsieh; Chih-Yang Huang; Jin-Ming Hwang (Molecular and Cellular Biochemistry, 2010)

Cost Considerations in Choosing Group Size for Group Testing in the Seed Potato Certification Program - Kuo-Szu Chiang; Sin-Hong Lai; Wen-Chuan Chung; Shang-Hu Lin; Tso-Chi Yang (American Journal of Potato Research, 2010)

Appraisal of affordable green subsidy of rice paddy in Taiwan - Chen-Wuing Liu; Shih-Wei Zhang; Hsing-Pin Yao; Kuo-Hua Lin; Wei-Taw Lin (Paddy and Water Environment, 2010)

Simultaneous declines in radon and methane precursory to 2008 M W 5.0 Antung earthquake: corroboration of in-situ volatilization - T. Kuo; W. Cheng; C. Lin; K. Fan; G. Chang; T. Yang (Natural Hazards, 2010)

E4BP4 is a cardiac survival factor and essential for embryonic heart development - Yi-Jiun Weng; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Tung-Yuan Lai; Hsi-Hsien Hsu; Chang-Hai Tsai; Fuu-Jen Tsai; Ding-Yu Lin; James A. Lin; Chih-Yang Huang; Kwong-Chung Tung (Molecular and Cellular Biochemistry, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Comparative analysis of temporal changes of multifunctionality benefit of two major rice paddy plains in Taiwan - Chen-Wuing Liu; Shih-Wei Zhang; Kuo-Hua Lin; Wei-Taw Lin (Paddy and Water Environment, 2010)

Estimation of aseismic crustal-strain using radon precursors of the 2003 M 6.8, 2006 M 6.1, and 2008 M 5.0 earthquakes in eastern Taiwan - T. Kuo; C. Lin; G. Chang; K. Fan; W. Cheng; C. Lewis (Natural Hazards, 2010)

Passenger thermal perceptions, thermal comfort requirements, and adaptations in short- and long-haul vehicles - Tzu-Ping Lin; Ruey-Lung Hwang; Kuo-Tsang Huang; Chen-Yi Sun; Ying-Che Huang (International Journal of Biometeorology, 2010)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Impact of GPS radio occultation data assimilation on regional weather predictions - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Chuen-Tsyr Terng; Fang-Ching Chien; Pay-Liam Lin; Mien-Tze Kueh; Shu-Hua Chen; Ming-Jen Yang; Chieh-Ju Wang; Anisetty S. K. A. V. Prasad Rao (GPS Solutions, 2010)

Effects of compressive residual stress on the morphologic changes of fibroblasts - Shu-Li Lin; Jen-Chang Yang; Kuo-Ning Ho; Chau-Hsiang Wang; Chien-Wu Yeh; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2009)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Trophic coupling between Synechococcus and pigmented nanoflagellates in the coastal waters of Taiwan, western subtropical Pacific - Lin Yun-Chi; Tsai An-Yi; Chiang Kuo-Ping (Journal of Oceanography, 2009)

Mitigation of micro vibration by viscous dampers - Tzu-Kang Lin; Chun-Chung Chen; Kuo-Chun Chang; Chu-Chieh Jay Lin; Jenn-Shin Hwang (Earthquake Engineering and Engineering Vibration, 2009)

Production of cyclodextrin glucanotransferase from an alkalophilic Bacillus sp. by pH-stat fed-batch fermentation - Chou-Chiang Kuo; Ching-An Lin; Jing-Yi Chen; Ming-Tse Lin; Kow-Jen Duan (Biotechnology Letters, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jen Liu (Apoptosis, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jeng Liu (Apoptosis, 2009)

Early transcriptional deregulation of hepatic mitochondrial biogenesis and its consequent effects on murine cholestatic liver injury - Mao-Meng Tiao; Tsu-Kung Lin; Cha-Wei Liou; Pei-Wen Wang; Jin-Bor Chen; Fang-Ying Kuo; Chao-Cheng Huang; Yao-Min Chou; Jiin-Haur Chuang (Apoptosis, 2009)

Detection of race 1 strains of Ralstonia solanacearum in field samples in Taiwan using a BIO-PCR method - Chih-Hung Lin; Shih-Tien Hsu; Kuo-Ching Tzeng; Jaw-Fen Wang (European Journal of Plant Pathology, 2009)

Mechanical interactions of cuspal-coverage designs and cement thickness in a cusp-replacing ceramic premolar restoration: a finite element study - Yen-Hsiang Chang; Wen-Hsueng Lin; Wen-Chieh Kuo; Chia-Yu Chang; Chun-Li Lin (Medical & Biological Engineering & Computing, 2009)

Investigating the adaptive model of thermal comfort for naturally ventilated school buildings in Taiwan - Ruey-Lung Hwang; Tzu-Ping Lin; Chen-Peng Chen; Nai-Jung Kuo (International Journal of Biometeorology, 2009)

Effects of Silver on the Photocatalytic Degradation of Gaseous Isopropanol - Chih-Ming Ma; Young Ku; Yu-Lin Kuo; Yiang-Chen Chou; Fu-Tien Jeng (Water, Air, & Soil Pollution, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

Isolation and characterization of microsatellite loci in the endangered freshwater fish Varicorhinus alticorpus (Cyprinidae) - Tzen-Yuh Chiang; Teh-Wang Lee; Feng-Jiau Lin; Kuo-Hua Huang; Hung-Du Lin (Conservation Genetics, 2008)

Isolation and characterization of 11 polymorphic microsatellite loci from Fatsia polycarpa (Araliaceae), an element of evergreen forests in Taiwan - Chi-Chun Huang; Kuo-Hsiang Hung; Tsai-Wen Hsu; Kuo-Hsiung Wang; Chi-Yung Lin; Tzen-Yuh Chiang (Conservation Genetics, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Chemical constituents of Antrodia camphorata submerged whole broth - Yi-Yuan Shao; Chin-Chu Chen; Hsin-Yi Wang; Hsi-Lin Chiu; Tzong-Hsiung Hseu; Yueh-Hsiung Kuo (Natural Product Research, 2008)

Direct displacement-based design for seismic retrofit of existing buildings using nonlinear viscous dampers - Yu-Yuan Lin; Kuo-Chun Chang; Chang-Yu Chen (Bulletin of Earthquake Engineering, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

5-Hydroxymethyl-2-furfural, a clinical trials agent for sickle cell anemia, and its mono/di-glucosides from classically processed steamed Rehmanniae Radix - An-Shen Lin; Keduo Qian; Yoshihide Usami; Li Lin; Hideji Itokawa; Charleson Hsu; Susan L. Morris-Natschke; Kuo-Hsiung Lee (Journal of Natural Medicines, 2008)

Study of growth and body composition of red snapper Lutjanus erythropterus fed diets containing Escherichia coli expressing recombinant tilapia insulin-like growth factor-I - Wen-Liang LIAO; Hsin-Hui LU; Shun-Kuo HUANG; Jen-Leh WU; Jan-Hsiung HUANG; En-Chung LIN (Fisheries Science, 2008)

Residual Stress Patterns Affect Cell Distributions on Injection-Molded Poly-l-Lactide Substrate - Sheng-Yang Lee; How Tseng; Keng-Liang Ou; Jen-Chang Yang; Kuo-Ning Ho; Che-Tong Lin; Haw-Ming Huang (Annals of Biomedical Engineering, 2008)

Induction of apoptosis in rabbit oral mucosa by 1.23% acidulated phosphate fluoride gel - Chia-Ling Tsai; Jui-Wei Lin; Hsi-Kung Kuo; Ming-Hong Tai; Yi-Chen Wu; Chih-Rong Shyr; Pei-Chang Wu (Archives of Toxicology, 2008)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

The frequency, intensity, and diurnal cycle of precipitation in surface and satellite observations over low- and mid-latitudes - Aiguo Dai; Xin Lin; Kuo-Lin Hsu (Climate Dynamics, 2007)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Allelopathy on Bark of Downed Logs of Chamaecyparis Obtusa sieb. and Zucc. var. formosana (Hayata) Rehder - Mei-Hwei Tseng; Wen-Rong Lai; Chin-Lin Hsieh; Yueh-Hsiung Kuo (Journal of Chemical Ecology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Pleomorphic extra-renal manifestation of the glomerular podocyte marker podocalyxin in tissues of normal beagle dogs - Wei-Ling Lin; Victor Fei Pang; Chen-Hsuan Liu; Jen-Yau Chen; Kuo-Fang Shen; Yu-Yu Lin; Chun-Ying Yu; Yung-Ho Hsu; Tzuu-Shuh Jou (Histochemistry and Cell Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Organization and promoter analysis of a tiger shrimp Penaeus monodon single WAP domain-containing protein gene - Jyh Yih CHEN; Jian Chyi CHEN; Sheng Hwa LIN; Chia Yu PAN; Ching Ming KUO (Fisheries Science, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Using Redox Potential to Detect Microbial Activities During Clavulanic Acid Biosynthesis in Streptomyces clavuligerus - Yun-Huin Lin; Sz-Chwun John Hwang; Jian Tong Gong; Jane-Yii Wu; Kuo-Cheng Chen (Biotechnology Letters, 2005)

Adsorption-elution purification of chimeric Bacillus stearothermophilus leucine aminopeptidase II with raw-starch-binding activity - Yu-Wen Hua; Meng-Chun Chi; Huei-Fen Lo; Lih-Ying Kuo; Kuo-Lung Ku; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

In Silico Analysis of Crustacean Hyperglycemic Hormone Family - S.H. Chen; C.Y. Lin; C.M. Kuo (Marine Biotechnology, 2005)

Histidines 345 and 378 of Bacillus stearotheromophilus leucine aminopeptidase II are essential for the catalytic activity of the enzyme - Guang-Yuh Hwang; Lih-Ying Kuo; Ming-Ru Tsai; Shin-Ling Yang; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

Isolation and characterization of a cellulolytic Geobacillus thermoleovorans T4 strain from sugar refinery wastewater - Shang-Kai Tai; Hsiu-Ping Pearl Lin; Jimmy Kuo; Jong-Kang Liu (Extremophiles, 2004)

Asymbiotic germination of immature seeds, plantlet development and ex vitro establishment of plants of Dendrobium tosaense makino—A medicinally improrant orchid - Shu-Fung Lo; Satish Manohar Nalawade; Chao-Lin Kuo; Chung-Li Chen; Hsin-Sheng Tsay (In Vitro Cellular & Developmental Biology - Plant, 2004)

PilR Enhances the Sensitivity of Xanthomonas axonopodis pv. citri to the Infection of Filamentous Bacteriophage Cf - Yen-Chun Yang; Chun-Ping Chou; Tsong-Teh Kuo; Shan-Hwa Lin; Mei-Kwei Yang (Current Microbiology, 2004)

Cloning of Two Crustacean Hyperglycemic Hormone Isoforms in Freshwater Giant Prawn ( Macrobrachium rosenbergii ): Evidence of Alternative Splicing - Shu-Hwa Chen; Chung-Yen Lin; Ching Ming Kuo (Marine Biotechnology, 2004)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)

Overexpression, Purification, and Characterization of the Recombinant Leucine Aminopeptidase II of Bacillus stearothermophilus - Lih-Ying Kuo; Guang-Yuh Hwang; Yu-Jing Lai; Shin-Ling Yang; Long-Liu Lin (Current Microbiology, 2003)

H2 production with anaerobic sludge using activated-carbon supported packed-bed bioreactors - Kuo-Shing Lee; Yung-Sheng Lo; Yung-Chung Lo; Ping-Jei Lin; Jo-Shu Chang (Biotechnology Letters, 2003)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

Optimization of glycerol feeding for clavulanic acid production by Streptomyces clavuligerus with glycerol feeding - Kuo-Cheng Chen; Yun-Huin Lin; Cheng-Min Tsai; Chen-Hao Hsieh; Jer-Yiing Houng (Biotechnology Letters, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Trophic functioning and nutrient flux in a highly productive tropical lagoon - Hsing-Juh Lin; Jia-Jang Hung; Kwang-Tsao Shao; Fancy Kuo (Oecologia, 2001)

Production and purification of recombinant Blomia tropicalis group 5 allergen from Pichia pastoris culture - Lin-Tang Goh; I-Chun Kuo; Sa Luo; Kaw Yan Chua; Moshe White (Biotechnology Letters, 2001)

UV-Induced Increase in RNA Polymerase Activity in Xanthomonas oryzae pathovar oryzae - Shan-Hua Lin; Hao-Jen Huang; Bei-Chang Yang; Tsong-Teh Kuo (Current Microbiology, 2001)

Surveys of Volatile Organic Compounds in Soil and Groundwater at Industrial Sites in Taiwan - M.-C. T. Kuo, C.-M. Chen, C. H. Lin, H. C (Bulletin of Environmental Contamination and Toxicology, 2000)

A simple method to determine urea concentration using intact Helicobacter pylori and BromoCresol Purple as a pH indicator - Yuh-Ling Lin; Chien-Tsu Chen; Su-Cheng Lin; Cheng Lee; Hsien-Shou Kuo; Chun-Mean Shih; Yuan-Hsun Hsu; Yi-Ping Chin; Err-Cheng Chan (Biotechnology Letters, 2000)

Azo dye decolorization with a mutant Escherichia coli strain - Jo-Shu Chang; Tai-Shin Kuo; Yun-Peng Chao; Jin-Yen Ho; Ping-Jei Lin (Biotechnology Letters, 2000)

Cloning of Two New cry Genes from Bacillus thuringiensis subsp. wuhanensis Strain - White-Shang Kuo; Jong-Huon Lin; Ching-Chou Tzeng; Shui-Shang Kao; Kin-Fu Chak (Current Microbiology, 2000)

The spectrum of microsatellite loci on chromosomes 7 and 8 in Taiwan aboriginal populations: a comparative population genetic study - Chi-Chen Wei; Fu-Tien Chiang; Kuo-Sin Lin; L.-I. Lin (Human Genetics, 1999)

Algicidal Effect of Peridinium bipes on Microcystis aeruginosa - Jiunn-Tzong Wu *, , Lin-Long Kuo-Huang; Jensen Lee (Current Microbiology, 1998)

Urinary N -acetyl-β-glucosaminidase as an indicator of renal dysfunction in electroplating workers - Chiu-Shong Liu; Hsien-Wen Kuo; Jim-Shoung Lai; Tsai-In Lin (International Archives of Occupational and Environmental Health, 1998)

Dietary flavonoids interact with trace metals and affect metallothionein level in human intestinal cells - Shiu-Ming Kuo; Penny S. Leavitt; Chih-Ping Lin (Biological Trace Element Research, 1998)

Nasal septum lesions and lung function in workers exposed to chromic acid in electroplating factories - Hsien-Wen Kuo; Jim-Shoung Lai; Tsai-In Lin (International Archives of Occupational and Environmental Health, 1997)

Effects of exposure to carbon disulfide (CS 2 ) on electrocardiographic features of ischemic heart disease among viscose rayon factory workers - Hsien-Wen Kuo; Jim-Shoung Lai; Mike Lin; Eai-Seung Su (International Archives of Occupational and Environmental Health, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Mutagenic Activity of Incense Smoke in Comparison to Formaldehyde and Acetaldehyde in Salmonella typhimurium TA102 - H. L. Chang; M. L. Kuo; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 1997)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)